Structured rheological solid personal care compositions
By using crystallizers and suspension agents in personal care compositions to form a mesh of fibrous crystalline particles, the problem of difficult to control the existing products during application and the uneven distribution of insoluble active agents is solved, and the shape and performance uniformity of the composition are achieved.
Patent Information
- Application Number
- CN202411908982.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2020-09-22
- Filing Date
- 2021-04-08
- Publication Date
- 2025-04-18
AI Technical Summary
Existing personal care compositions are difficult to control when administered, and the insoluble active agents are unevenly distributed in the composition, resulting in uneven performance.
Rheological solid compositions containing crystallizers, suspensions, insoluble active substances and aqueous phases are used to form a web of fibrous crystalline particles through thermal heating and cooling processes to prevent pasting or precipitation of the insoluble active agent.
The shape maintenance of the rheological solid composition and the uniform suspension of insoluble active agents are achieved, solving the problems of dirty and uneven performance of existing products.
Smart Images

Figure CN119837824A_ABST
Abstract
Description
[0001] This application is a divisional application. The application date of the original application is April 8, 2021, the application number is 202180027538.X (PCT / US2021 / 026313), and the name of the invention is “Structured rheological solid personal care composition”. Technical Field
[0002] Described herein are rheologically solid liquid extruded personal care compositions comprising greater than about 55% water with a crystallizing agent having an elongated fibrous crystal habit. Wherein the rheologically solid personal care composition allows for a unique "crunchy" skin feel and / or glide when rubbed on the skin; and provides enhanced evaporative cooling to achieve a fresh / cooling feel, even in the absence of a sensate. Background Art
[0003] Consumers use personal care compositions for chest, back and / or throat daily to relieve nasal congestion, dry cough, chest tightness, muscle aches and / or pain, sleep difficulties caused by colds and / or flu, and / or provide relief on the skin. Current products are formulated into creams, lotions and / or ointments, and are applied to the skin by hand, which may be messy and difficult to control when applying the product due to their liquid or semi-liquid properties. Such products may also leave a greasy feeling on the user's hands after application and / or may leave stains on clothes and sheets. In addition, some consumers may wish to apply such products repeatedly throughout the day or when busy, without having to wash their hands after application. Therefore, a more convenient, non-messy delivery system for personal care compositions is needed.
[0004] Conventional soap-type gel bars are often used as deodorants for underarm applications and typically incorporate sodium stearate (C18) gelling agent, which is actually a mixture of various chain lengths derived from natural sources of stearic acid esters (usually tallow). The use of sodium stearate requires the inclusion of high levels of polyols (e.g., propylene glycol and glycerol) as solubilization aids for the gelling agent during processing, even at high process temperatures. Typical compositions contain about 50% propylene glycol, 25% glycerol, and only 25% water (EP2170257 and EP2465487). This eliminates the astringent feel of the solid bar and reduces the slip and cool feel. Finally, this may require high levels of gelling agents, including gelling agents other than sodium stearate, to prepare gel sticks, especially translucent gel sticks.
[0005] Attempts have been made to provide rheological solid compositions similar in composition to those embodied in the present invention, which contain insoluble active agents such as flavor capsules, solid particles, or oil droplets, because rheological solid compositions provide users with a way to quickly and easily apply the rheological solid composition to a particular surface. However, these products fail to stabilize the insoluble active agent in the composition, causing the insoluble active agent to float to the top (i.e., "creaming") or sink to the bottom (i.e., "sedimentation") before the composition solidifies. If the insoluble active agent is not evenly distributed, the rheological solid composition may have a higher concentration of insoluble active agent in one area than in another area, resulting in uneven performance during the service life of the product. In the most extreme case, it is unacceptable for a consumer product to have a significant amount of insoluble active material at the top and / or bottom of the product; it is most preferred to have the insoluble active material evenly dispersed throughout the product.
[0006] Therefore, there is a need to provide a rheologically solid personal care composition having low levels of gelling agents, which can retain its shape and which contains insoluble active benefit agents uniformly suspended in the composition. Summary of the invention
[0007] Provided herein is a rheological solid personal care composition comprising a crystallizing agent; a suspending agent; an insoluble active material; and an aqueous phase.
[0008] Additionally, provided are rheological solid compositions for use in methods of treating nasal congestion, colds, flu, coughs, dry coughs, chest tightness, muscle aches and pains, or any combination thereof.
[0009] In addition, a method for producing a rheological solid composition is provided, the method comprising the steps of:
[0010] - providing and heating an aqueous solution of sodium chloride and sodium hydroxide,
[0011] - adding an emulsifier, preferably palmitic acid, so as to obtain an emulsifier master mix, preferably a sodium palmitate soap master mix,
[0012] - adding suspending agents, preferably xanthan gum and glycerol, to the emulsifier main mixture,
[0013] - adding an insoluble active premix, preferably a vaseline-based premix of topical actives, preferably selected from the group consisting of menthol, nutmeg, camphor, eucalyptus, cedar leaf, thymol and any combination thereof, to the emulsifier main mixture to obtain a blend,
[0014] - cooling said blend so as to form a crystalline structure of said rheological solid composition,
[0015] - Optionally adding a hygroscopic stabilizer to the blend in order to stabilize the crystalline structure, the hygroscopic stabilizer is preferably sodium lactate. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Although the specification ends with claims that specifically point out and clearly claim what is considered to be the subject matter of the present disclosure, it is believed that the present disclosure can be more fully understood from the following description in conjunction with the accompanying drawings. Some of these figures may have been simplified by omitting selected elements in order to more clearly show other elements. Such omissions of elements in certain figures do not necessarily indicate the presence or absence of a particular element in any exemplary embodiment unless such is clearly described in the corresponding text description. The drawings are not drawn to scale.
[0017] Figure 1A . Top view showing the separation of active substance in the absence of suspending agent.
[0018] Figure 1B . Side view showing the separation of active substance in the absence of a suspending agent.
[0019] Figure 2A .Top view showing no separation of active material in the presence of suspending agent.
[0020] Figure 2B .Side view showing no separation of active material in the presence of a suspending agent.
[0021] Figure 3 .SEM of a crystalline network formed by fibrous particles.
[0022] Figure 4 .An effective gum suspending agent system for stabilizing insoluble active particles.
[0023] Figure 5 .The effect of gum suspension on the effectiveness of different crystallization agents.
[0024] Figure 6 .Total fragrance extrusion (concentration in ppm) versus time (hours). DETAILED DESCRIPTION
[0025] The present invention includes a rheological solid personal care composition containing a crystalline network. The crystalline network ("network") comprises a relatively rigid, three-dimensional, interlocking crystalline skeleton of fibrous crystalline particles (formed by a crystallizing agent) having voids or openings containing an aqueous solution and optionally one or more active substances. The network provides a self-supporting structure so that the rheological solid personal care composition can be "self-standing" when placed on a surface. If compressed above a critical stress, the network allows the rheological solid personal care composition to extrude the trapped aqueous solution, and optionally one or more active substances. The rheological solid personal care composition of the present invention comprises a crystallizing agent, a suspending agent, an insoluble active substance, and an aqueous phase, and can be combined with a device to enable application.
[0026] As used herein, "personal care composition" refers to compositions intended for topical application to the skin, including topical prescription medications, over-the-counter medications, behind-the-counter medications, cosmetics, consumer products, and combinations thereof.
[0027] Crystallization agent
[0028] In the present invention, the network of the rheological solid personal care composition comprises fibrous crystalline particles formed by a crystallizing agent; wherein the "crystallizing agent" as used herein comprises a sodium salt of a fatty acid having a shorter chain length (C12-C20), such as sodium palmitate (C16), in a large portion of water. The rheological solid personal care composition is best achieved using a "narrow" distribution of crystallizing agent chain lengths, and is further best achieved in combination with a controlled crystallization process in the absence of very short chain lengths (C12 or shorter) and a measurable amount of unsaturated groups on the chain of the fatty acid sodium salt. Those skilled in the art recognize that the crystalline particles exhibit a sharp scattering peak between 0.25 degrees - 60 degrees 2θ in powder x-ray diffraction measurements. This is in stark contrast to compositions in which these materials are used as gelling agents, which exhibit broad amorphous scattering peaks resulting from poorly formed solids.
[0029] The rheological solid personal care composition may comprise greater than about 55% water, alternatively greater than about 60%, alternatively greater than about 65%, alternatively greater than about 70% water, alternatively greater than about 80% water, and is "structured" by a network of predominantly single chain long interlocking fibrous crystalline particles, as described above (see Figure 3). The term "fibrous crystalline particles" refers to particles in which the length of the particle in the direction of its longest axis is 10 times the length of the particle in any orthogonal direction. The fibrous crystalline particles prepare a network at very low concentrations (about 0.5% by weight) that forms a solid that is produced only under minimal applied stress, i.e., a rheological solid. The suspending agent, insoluble active substance and aqueous phase (water) are primarily present in the open spaces of the network. In preparing these compositions, heat is used to dissolve the crystallizing agent in water. As the mixture cools for several minutes to several hours, the fibrous crystalline particles form a network. Without being bound by theory, suspending agents (such as polymer gums, clay particles and hydrophobic fat particles) prevent the insoluble active substance from creaming or settling during the formation of the network (see Figure 1A and Figure 1B ); removal of the suspending agent showed significant (or catastrophic) separation of the insoluble active material. Preferred compositions have a Phase Stability Rating of "1", and most preferably a Phase Stability Rating of "2", as determined by the Phase Stability Test Method described herein.
[0030] Without being limited to theory, it is believed that only sodium salts of fatty acids with high chain lengths can be used as crystallizing agents in the present invention. Crystallizing agents comprising shorter chain lengths (C12 or shorter) can make the composition highly soluble at room temperature, so that fibrous crystalline particles are not formed. The inclusion of unsaturation in the chain of the fatty acid sodium salt increases the "twist" of excessive crystallization, so that fibrous crystalline particles are not formed, and the composition is a paste or liquid. Crystallizing agents should be present in sufficient amounts to form a rheological solid with a firmness between about 0.1N and about 50.0N, more preferably between about 0.5N-about 40.0N, more preferably between about 1.0N-about 30.0N and most preferably between about 2.5N-about 15.0N, wherein the lower limit is for the composition to set the minimum "softness", and the upper limit is for the composition to set the maximum "hardness", both of which are affected by the application of consumer products. In some aspects, the crystallizing agent is present in an amount of about 0.01% to about 10% by weight of the rheological solid personal care composition. The crystallizing agent may be present in an amount from about 0.1% to about 7% by weight of the rheological solid personal care composition, from about 1% to about 7% by weight of the rheological solid personal care composition, or from about 2% to about 5% by weight of the rheological solid personal care composition.
[0031] The crystallizing agent should form elongated fibrous crystalline particles, wherein the length of the particle in the direction of its longest axis is preferably 10 times, more preferably 15 times and most preferably 20 times the length of the particle in any orthogonal direction, as assessed by standard scanning electron microscopy (SEM) methods. Without being bound by theory, it is believed that longer crystalline particles are more effectively able to entangle, thereby forming an effective network structure. This is in contrast to the fatty acid crystals of magnesium salts of fatty acids (protonated form of sodium salts of fatty acids), which are not elongated and generally exhibit a ratio of 1 to 2 times. The composition of the fibrous crystalline particles should be thermally stable at room temperature, preferably at a temperature above about 30°C, more preferably above about 35°C, more preferably above about 40°C, more preferably above about 50°C, and most preferably above about 60°C, as determined by the Thermal Stability Test Method as described herein. Finally, the fibrous crystalline particles combine to form a network so that the aqueous phase and insoluble active materials can be extruded from the rheological solid personal care composition with a defined applied stress. The work required to extrude the water phase from 15% of the structure volume of the rheological solid personal care composition is preferably between about 100 J m-3 and about 6000 J m-3, alternatively between about 100 J m-3 and about 3000 J m-3, alternatively between about 300 J m-3 and about 2000 J m-3, alternatively between about 500 J m-3 and about 1500 J m-3, as determined by the Water Extrusion Test Method described herein.
[0032] In some aspects, the crystallizing agent can be a metal salt. Non-limiting examples of metal salts can include sodium stearate, sodium palmitate, potassium stearate, potassium palmitate, sodium myristate. Those skilled in the art will appreciate that the rheological solid personal care composition can be prepared using the acid form of the salt in combination with a base such as sodium hydroxide to form a metal salt.
[0033] Suspension
[0034] Suspending agents prevent the separation of insoluble active substances when preparing rheological solid personal care compositions. The composition of the present invention is heated until the crystallizing agent dissolves, leaving the dispersed active substance in the low viscosity fluid. When the composition cools, the crystallizing agent begins to form fibrous crystalline particles, which are woven together into a mesh that eventually captures the active substance. This process may take minutes to hours. Without being bound by theory, it is believed that the suspending agent increases viscosity or forms a yield stress that keeps the active substance from creaming or settling during the crystallization of the crystallizing agent and the formation of the mesh. Preferred suspending agents are effective at low concentrations to prevent potential negative effects on the mesh and consumer product performance. Preferred levels are less than about 2% by weight, alternatively less than about 1% by weight, alternatively less than about 0.5% by weight, and alternatively less than about 0.1% by weight. In some aspects, the rheological solid personal care composition may comprise from about 0.01 wt % to about 2 wt %, alternatively from about 0.05 wt % to about 1 wt %, alternatively from about 0.1 wt % to about 0.5 wt %, alternatively from about 0.25 wt % to about 0.35 wt % of a suspending agent, all percentages being based on the weight of the rheological solid personal care composition.
[0035] Suitable suspending agents include gums, polymers, microfiber particles, clay particles, and combinations thereof, and surprisingly, the composition must be selected so that their addition does not have a negative impact on the network. For example, the use of gums can weaken the network structure relative to compositions without gums that require an increased amount of crystallization (Example 2). As another example, the use of clay (Example 10) and microfibers (Example 9) can be rendered ineffective by the addition of sodium chloride.
[0036] gum
[0037] The rheological solid personal care composition comprises at least one suspending agent to keep insoluble materials (i.e., solids or oils) suspended during preparation. The suspending agent may comprise one or more biopolymers. Non-limiting examples of such biopolymers include polysaccharides such as polymers of glucose, fructose, galactose, mannose, rhamnose, glucuronic acid, and mixtures thereof.
[0038] The suspending agent may be in the form of a polysaccharide or a mixture of polysaccharides. Preferred polysaccharide suspending agents include xanthan gum, glucomannan, galactomannan and combinations thereof. Glucomannan may be derived from natural gums such as konjac gum. Galactomannan may be derived from natural gums such as locust bean gum. The polysaccharide suspending agent may also include carrageenan. The suspending agent gum may be modified, such as by deacetylation.
[0039] The rheological solid personal care composition may comprise a polysaccharide suspending agent system comprising at least two polysaccharides, such as a first polysaccharide and a second polysaccharide. The first polysaccharide may be xanthan gum. The second polysaccharide may be selected from the group consisting of glucomannan, galactomannan, and combinations thereof. The second polysaccharide may be selected from the group consisting of konjac gum, locust bean gum, tara bean, and combinations thereof.
[0040] Preferably, the first polysaccharide is xanthan gum and the second polysaccharide is konjac gum.
[0041] The first polysaccharide may be present at a level greater than about 10 wt % and less than about 100 wt %, alternatively about 40 wt % to about 90 wt %, alternatively about 40 wt % to about 60 wt % by weight of the polysaccharide suspending concentrate system.
[0042] The second polysaccharide may be present at a level of about 0 wt % to about 90 wt %, alternatively about 60 wt % to about 10 wt %, alternatively about 60 wt % to about 40 wt % by weight of the polysaccharide suspending concentrate system.
[0043] The total concentration of polysaccharides present in the rheological solid personal care composition may be between about 0.01 wt % and about 1.0 wt %, or more preferably between about 0.03 wt % and about 1.0 wt %, or more preferably between about 0.05 wt % and about 0.8 wt %, more preferably between about 0.07 wt % and about 0.75 wt %, and most preferably between about 0.09 wt % and about 0.5 wt %, all percentages being by weight of the rheological solid personal care composition. Without being bound by theory, it is believed that minimizing the total polysaccharide level in the composition ensures stability of the dispersed active agent during preparation while minimizing the effect of the suspending agent on the network structure.
[0044] The polysaccharide suspending concentrate system may have a weight average molecular weight ranging from about 10,000 Daltons to about 15,000,000 Daltons, alternatively from about 200,000 Daltons to about 10,000,000 Daltons, alternatively from about 300,000 Daltons to about 6,000,000 Daltons, alternatively from about 300,000 Daltons to about 500,000 Daltons.
[0045] The polysaccharide suspension system can be characterized by an average acetylation ratio, wherein the average acetylation ratio is the number of acetylated hydroxyl groups in the polysaccharide divided by the number of free hydroxyl groups in the polysaccharide. The average acetylation ratio can be in the range of about 2.0 to about 0.5, preferably in the range of about 1.5 to about 0.5.
[0046] clay
[0047] In the present disclosure, suspending agents can be used to provide viscosity and thixotropic properties to the composition, thereby preventing the suspended active agent particles from creaming or settling during preparation. In one or more embodiments, the suspending agent can be a mineral clay mixture, more specifically an organophilic mineral clay mixture. In one or more embodiments, the mineral clay mixture can be treated with an alkyl quaternary ammonium compound to make the mineral clay mixture hydrophobic; such clays can also be referred to as organophilic. In one or more embodiments, the mineral clay mixture may include: mineral clay (a), which contains about 50% to about 95% by weight, or about 60% to about 95% by weight, or about 70% to about 90% by weight of mineral clay based on the weight of the mineral clay mixture, the mineral clay selected from the group consisting of sepiolite, palygorskite, and a mixture of sepiolite and palygorskite; and mineral clay (b), which contains montmorillonite in an amount of the balance by weight of the mineral clay mixture. In one or more embodiments, the smectite can be a natural or synthetic clay mineral selected from the group consisting of hectorite, laponite, montmorillonite, bentonite, beidellite, saponite, stavanite, and mixtures thereof. Suitable clays include laponites from the Garamite product line available from BYK Additives, (Gonzalez, TX).
[0048] Microfiber
[0049] Any microcrystalline cellulose may be employed in the compositions of the present invention. Suitable raw materials include, for example, wood pulp such as bleached sulfite and sulfate pulp, corn husks, bagasse, wheat straw, cotton, cotton linters, flax, hemp, ramie, fermented cellulose, and the like. The amounts of microcrystalline cellulose and hydrocolloid may vary over a wide range depending on the desired properties in the final composition. Suitable microfibers include Rheocrysta c-2sp (WASE COSFA USA, Inc.).
[0050] Insoluble active substances
[0051] In addition to the fibrous crystalline particles comprising the mesh, the rheological solid personal care composition may also include one or more insoluble active particles. As used herein, "insoluble active particles" include at least a portion of solid, semisolid or liquid material, including an amount of insoluble active substances. The insoluble active particles can take various forms, for example, the insoluble active particles can be 100% solid by weight or can be hollow. The insoluble active particles can include, for example, mesoporous particles, activated carbon, zeolites, beneficial agent delivery particles, waxes, insoluble oils, hydrogels and / or ground nut shells.
[0052] In some aspects, the rheological solid personal care composition may comprise from about 0.001 wt % to about 35 wt % insoluble active particles, alternatively from about 0.01 wt % to about 30 wt % insoluble active particles, alternatively from about 0.01 wt % to about 25 wt %, alternatively from about 0.1 wt % to about 15 wt %, alternatively from about 0.5 wt % to about 12 wt %, alternatively from about 1 wt % to about 10 wt %, alternatively from about 5 wt % to about 10 wt % insoluble active particles, all percentages being based on the weight of the rheological solid personal care composition.
[0053] In some aspects, the rheological solid personal care composition may comprise from about 0.001 wt % to about 30 wt %, alternatively from about 0.1 wt % to about 30 wt %, alternatively from about 0.1 wt % to about 25 wt %, alternatively from about 0.5 wt % to about 15 wt %, alternatively from about 1 wt % to about 10 wt %, alternatively from about 5 wt % to about 15 wt % of an insoluble active agent, all percentages being based on the weight of the rheological solid personal care composition.
[0054] The rheological solid personal care composition may comprise one or more types of insoluble active particles, for example, two types of insoluble active particles, wherein one of the first insoluble active particle or the second insoluble active particle (a) is made of a different material than the other; (b) has a wall comprising a different amount of wall material or monomer than the other; (c) contains a different amount of a fragrance oil component than the other; (d) contains different fragrance oils; (e) has a wall that is cured at a different temperature; (f) contains fragrance oils with different cLogP values; (g) contains fragrance oils with different volatilities; (h) contains fragrance oils with different boiling points; (i) has a wall made with different weight ratios of wall materials; (j) has a wall that cures at a different cure time; and / or (k) has a wall that is heated at a different rate.
[0055] The plurality of insoluble active agent particles may have a diameter of less than about 500 μm, alternatively less than about 400 μm, alternatively less than about 300 μm, alternatively less than about 200 μm, alternatively less than about 100 μm. Those skilled in the art recognize that the ability to suspend particles is a function of the average diameter of the particles (where larger particles are more difficult to suspend) and a function of the total amount of particles (where larger particles are more difficult to suspend).
[0056] For the former, those skilled in the art also recognize that the concentration of the suspending agent with a given insoluble active agent may have to be increased to accommodate larger insoluble active particles. It is generally preferred to minimize the amount of suspending agent (e.g., Example 2) so that smaller active agent particles are preferred. For the latter, those skilled in the art also recognize that the concentration of the suspending agent with a given insoluble active agent may have to be increased to accommodate larger amounts of insoluble active particles (e.g., Example 7).
[0057] Encapsulated Insoluble Benefit Agents
[0058] The insoluble active particles may comprise a wall material encapsulating the insoluble active. The insoluble active may be selected from the group consisting of: a fragrance composition, a fragrance raw material, a fragrance, a skin coolant, a vitamin, a sunscreen, an antioxidant, a glycerin, a bleach encapsulate, a chelating agent, an antistatic agent, an insect and moth repellent, a colorant, an antioxidant, a sanitizer, a disinfectant, a microbial control agent, a mold control agent, a mildew control agent, an antiviral agent, a desiccant, a stain repellent, a detergent, a chlorine bleach odor control agent, a dye fixative, a dye transfer inhibitor, a color preserving agent, an optical brightener, a color restoration / rejuvenating agent, an anti-fading agent, Whiteness enhancers, anti-abrasion agents, anti-wear agents, fabric integrity agents, anti-wear agents, anti-pilling agents, defoaming agents, defoaming agents, UV protectants, light fade inhibitors, anti-allergenic agents, enzymes, water repellents, fabric comfort agents, anti-shrinkage agents, anti-stretching agents, stretch recovery agents, skin care agents, natural active substances, antimicrobial active substances, antiperspirant active substances, cationic polymers, dyes, metal catalysts, non-metal catalysts, activators, pre-formed peroxycarboxylic acids, diacyl peroxides, hydrogen peroxide sources, enzymes, topical active substances and combinations thereof. As used herein, "fragrance raw materials" refers to one or more of the following ingredients: fragrance essential oils; fragrance compounds; pre-fragrances; materials provided with fragrance essential oils, fragrance compounds and / or pre-fragrances, including stabilizers, diluents, processing aids and contaminants; and any materials that usually accompany fragrance essential oils, fragrance compounds and / or pre-fragrances.
[0059] The wall material of insoluble active particles can include melamine, polyacrylamide, silicone, silicon dioxide, polystyrene, polyurea, polyurethane, materials based on polyacrylate, materials based on polyacrylate, gelatin, styrene malic anhydride, polyamide, aromatic alcohol, polyvinyl alcohol and their mixtures. Melamine wall materials can include melamine cross-linked with formaldehyde, melamine-dimethoxyethanol cross-linked with formaldehyde and their mixtures. Polystyrene wall materials can include polystyrene cross-linked with divinylbenzene. Polyurea wall materials can include urea cross-linked with formaldehyde, urea cross-linked with glutaraldehyde, polyisocyanates reacted with polyamines, polyamines reacted with aldehydes and their mixtures. Wall materials based on polyacrylate can include polyacrylate formed by methyl methacrylate / dimethylaminomethyl methacrylate, polyacrylate formed by amine acrylate and / or methacrylate and strong acid, polyacrylate formed by carboxylic acid acrylate and / or methacrylate monomer and strong base, polyacrylate formed by amine acrylate and / or methacrylate monomer and carboxylic acid acrylate and / or carboxylic acid methacrylate monomer, and their mixtures.
[0060] Wall materials based on polyacrylic acid esters may include polyacrylic acid esters formed from alkyl and / or glycidyl esters of acrylic acid and / or methacrylic acid, acrylates and / or methacrylates carrying hydroxyl and / or carboxyl groups, and allyl glucamide, and mixtures thereof.
[0061] Wall materials based on aromatic alcohols include aryloxyalkanols, arylalkanols and oligomeric alkanol aryl ethers. They may also contain aromatic compounds with at least one free hydroxyl group, particularly preferably at least two directly aromatically coupled free hydroxyl groups, wherein it is particularly preferred if at least two free hydroxyl groups are directly coupled to an aromatic ring and more particularly preferably positioned in the meta position relative to each other. Preferably, the aromatic alcohol is selected from phenol, cresols (o-cresol, m-cresol and p-cresol), naphthols (α-naphthol and β-naphthol) and thymol, as well as ethylphenol, propylphenol, fluorophenol and methoxyphenol.
[0062] The polyurea-based wall material may comprise a polyisocyanate. The polyisocyanate may be an aromatic polyisocyanate containing a phenyl, toluyl, xylyl, naphthyl or diphenyl moiety (e.g., a polyisocyanurate of toluene diisocyanate, a trimethylolpropane adduct of toluene diisocyanate or a trimethylolpropane adduct of xylylene diisocyanate), an aliphatic polyisocyanate (e.g., a trimer of hexamethylene diisocyanate, a trimer of isophorone diisocyanate and a biuret of hexamethylene diisocyanate) or a mixture thereof (e.g., a mixture of a biuret of hexamethylene diisocyanate and a trimethylolpropane adduct of xylylene diisocyanate). In other embodiments, the polyisocyanate can be cross-linked and the cross-linking agent is a polyamine (e.g., diethylenetriamine, bis(3-aminopropyl)amine, bis(hexylene)triamine, tris(2-aminoethyl)amine, triethylenetetramine, N,N'-bis(3-aminopropyl)-1,3-propylenediamine, tetraethylenepentamine, pentaethylenehexamine, branched polyethyleneimine, chitosan, nisin, gelatin, 1,3-diaminoguanidine monohydrochloride, 1,1-dimethylbiguanidine hydrochloride, or guanidine carbonate).
[0063] The polyvinyl alcohol-based wall material may comprise a cross-linked hydrophobically modified polyvinyl alcohol comprising a cross-linker comprising i) a first dextran aldehyde having a molecular weight of about 2,000 Da to about 50,000 Da; and ii) a second dextran aldehyde having a molecular weight of greater than about 50,000 Da to about 2,000,000 Da.
[0064] Preferably, the insoluble active particles with fragrance have a wall material comprising silica or a polymer of acrylic acid or its derivatives and the benefit agent comprises a fragrance mixture.
[0065] For insoluble active particles, the rheological solid personal care composition may comprise from about 0.001 wt % to about 20 wt % of a benefit agent contained in the wall material of the benefit agent delivery particles, based on the weight of the rheological solid personal care composition. Alternatively, the rheological solid personal care composition may comprise from about 0.01 wt % to about 10 wt %, or most preferably from about 0.05 wt % to about 5 wt % of a benefit agent contained in the wall material of the insoluble active particles, based on the weight of the rheological solid personal care composition.
[0066] These walled particles may be coated with a deposition aid, a cationic polymer, a nonionic polymer, an anionic polymer or a mixture thereof. Suitable polymers may be selected from polyvinyl formaldehyde, partially hydroxylated polyvinyl formaldehyde, polyvinyl amine, polyethylene imine, ethoxylated polyethylene imine, polyvinyl alcohol, polyacrylates, and combinations thereof.
[0067] Unencapsulated spices
[0068] The rheological solid personal care composition may contain an unencapsulated perfume comprising one or more perfume raw materials that provide only hedonic benefits (i.e., not neutralizing malodors, but providing a pleasant scent). Suitable perfumes are disclosed in US 6,248,135. For example, the rheological solid personal care composition may contain a mixture of volatile aldehydes for neutralizing malodors and hedonic perfume aldehydes.
[0069] When a fragrance other than the volatile aldehyde in the malodor control component is formulated into the rheological solid personal care composition, the total amount of fragrance and volatile aldehyde may be from about 0.015 wt. % to about 2 wt. %, alternatively from about 0.01 wt. % to about 1.0 wt. %, alternatively from about 0.015 wt. % to about 0.5 wt. %, based on the weight of the rheological solid personal care composition.
[0070] Fragrance delivery technology
[0071] The rheological solid personal care composition may comprise one or more fragrance delivery technologies that stabilize and enhance the deposition and release of fragrance ingredients from the treated substrate. Such fragrance delivery technologies may also be used to extend the persistence of fragrance release from the treated substrate. Fragrance delivery technologies, methods of preparing certain fragrance delivery technologies, and uses of such fragrance delivery technologies are disclosed in US 2007 / 0275866A1.
[0072] The rheological solid personal care composition may comprise from about 0.001 wt % to about 20 wt %, or from about 0.01 wt % to about 10 wt %, or from about 0.05 wt % to about 5 wt %, or even from about 0.1 wt % to about 0.5 wt % of a fragrance delivery technology. In one aspect, the fragrance delivery technology may be selected from the group consisting of pro-fragrances, polymer particles, soluble silicones, polymer-assisted delivery, molecule-assisted delivery, assisted delivery, amine-assisted delivery, cyclodextrins, starch encapsulation blends, zeolites, and inorganic carriers, and mixtures thereof.
[0073] The fragrance delivery technology may include amine reaction products (ARPs) or thioreaction products. One may also use "reactive" polymeric amines and / or polymeric thiols, in which amine and / or thiol functional groups are pre-reacted with one or more PRMs to form a reaction product. Typically, reactive amines are primary and / or secondary amines, and may be part of a polymer or a monomer (non-polymer). Such ARPs may also be mixed with additional PRMs to provide the benefits of polymer-assisted delivery and / or amine-assisted delivery. Non-limiting examples of polymeric amines include polymers based on polyalkylimines, such as polyethyleneimine (PEI) or polyethyleneamine (PVAm). Non-limiting examples of monomeric (non-polymeric) amines include hydroxylamines, such as 2-aminoethanol and its alkyl-substituted derivatives, and aromatic amines such as anthranilates. ARPs may be pre-mixed with fragrances, or added separately to wash-off or rinse-off applications. On the other hand, materials containing heteroatoms (e.g., oxygen, phosphorus, or selenium) other than nitrogen and / or sulfur may be used as substitutes for amine compounds. On the other hand, the aforementioned alternative compounds may be used in combination with amine compounds. In another aspect, a single molecule may comprise an amine moiety and one or more alternative heteroatom moieties, such as thiols, phosphines, and selenols. Beneficial effects may include improved delivery of fragrances and controlled fragrance release. Suitable ARPs and methods of making them are found in USPA 2005 / 0003980 A1 and USP 6,413,920 B1.
[0074] Essential and natural oils
[0075] Insoluble active particles may include a separate mixture of insoluble oils such as essential oils and natural oils. As used herein, the term "essential oil" refers to an oil or extract distilled or squeezed from a component of a plant and these oils. Typical essential oils and their main components are, for example, those obtained from: thyme (thymol, carvacrol), oregano (carvacrol, terpenes), lemon (limonene, terpinene, phellandrene, pinene, citral), lemongrass (citral, methylheptenone, citronellal, geraniol), orange flower (linalool, β-pinene, limonene), orange (limonene, citral), anise (anethole, safrole), cloves (eugenol, eugenol acetate, caryophyllene), rose (geraniol, citronellol), rosemary (borneol, borneol esters, camphor), geranium (geraniol, citronellol, linalool ), lavender (linalyl acetate, linalool), citronella (geraniol, citronellol, citronellal, camphene), eucalyptus (cineole); mint (menthol, menthyl ester), spearmint (carvone, limonene, pinene), wintergreen (methyl salicylate), camphor (safrole, acetaldehyde, camphor), laurel (eugenol, myrcene, eugenol), cinnamon (cinnamaldehyde, cinnamyl acetate, eugenol), tea tree (terpinen-4-ol, cineole), eucalyptus oil, nutmeg oil, turpentine oil, chamomile oil, neroli, cedar leaf (α-thujone, β-thujone, fenchone) and combinations thereof. Essential oils are widely used in spices and as flavoring agents, drugs and solvents. Essential oils (their composition and preparation) are described in detail in Kirk-Othmer Encyclopedia of Chemical Technology 4th edition and The Merck Index 13th edition.
[0076] In some aspects, the rheological solid personal care composition may comprise from about 0.1 wt % to about 20 wt %, alternatively from about 0.5 wt % to about 15 wt %, alternatively from about 1 wt % to about 12 wt %, alternatively from about 4 wt % to about 15 wt %, alternatively from about 5 wt % to about 10 wt % of an insoluble oil, all percentages being based on the weight of the rheological solid personal care composition.
[0077] Wax and oil
[0078] Insoluble active particles can comprise a separate mixture of wax and oil as a non-aqueous vehicle.Non-aqueous vehicles are typically any chemical substance in any physical form that is free of water.Non-aqueous vehicles can be selected from the group consisting of free liquid vaseline, vaseline, mineral oil, glycerine, natural and synthetic oils, fats, silicones and silicone derivatives, polyvinyl acetate, natural and synthetic waxes such as animal waxes such as beeswax, lanolin and shellac, hydrocarbons, hydrocarbon derivatives, vegetable oil waxes such as carnauba wax, candelilla wax and bayberry wax, vegetable oils such as caprylic / capric triglycerides and their combinations. In some respects, the non-aqueous vehicle can be selected from the group consisting of free liquid vaseline, vaseline, mineral oil, vegetable oil such as almond oil, canola oil, squalane, squalene, coconut oil, corn oil, jojoba oil, jojoba wax, lecithin, olive oil, safflower oil, sesame oil, shea butter, soybean oil, sweet almond oil, sunflower oil, tea tree oil, shea butter, palm oil and animal oil such as fish oil and oleic acid and their mixture. In some respects, the non-aqueous vehicle can be mineral oil. In some respects, the non-aqueous vehicle can be pentaerythritol tetraisostearate.
[0079] Preferably, the non-aqueous vehicle is hydrophobic. One advantage of adding a hydrophobic non-aqueous vehicle such as petrolatum is thermal stability. Without being bound by theory, it is believed that adding a hydrophobic non-aqueous vehicle can provide better partitioning between the oil phase and the water phase, which can provide thermal stability. In addition, the hydrophobic non-aqueous vehicle can improve the hardness and spreadability of the rheological solid personal care composition.
[0080] In some aspects, the rheological solid personal care composition may comprise from about 1 wt % to about 15 wt %, alternatively from about 3 wt % to about 12 wt %, alternatively from about 5 wt % to about 10 wt % of a non-aqueous vehicle, all percentages being based on the weight of the rheological solid personal care composition.
[0081] In some aspects, the rheological solid personal care composition can comprise a ratio of insoluble active to non-aqueous vehicle of from about 1 to about 2, alternatively from about 1.5 to about 1.9.
[0082] Deodorant
[0083] The rheological solid personal care composition may contain other malodor reduction technologies. This may include, but is not limited to, amine functional polymers, metal ions, cyclodextrins, cyclodextrin derivatives, polyols, oxidants, activated carbon, zeolites, and combinations thereof.
[0084] Touch modifier
[0085] The rheological solid personal care composition may also contain an insoluble active agent designed to modify the tactile properties of the composition when applied to a surface such as the skin. This may include starch (e.g., tapioca starch, rice starch, etc.), talc, fumed silica ( 200), titanium dioxide, dimethicone, iron oxide, mica, charcoal, colloidal oatmeal, colloidal cellulose, kaolin, and combinations thereof.
[0086] Skin care products
[0087] Skin care agents may be added to deliver therapeutic and / or skin protection benefits. It should be recognized that among the various materials that can be used in compositions for delivery to the skin, those that are considered safe and effective skin care agents and mixtures thereof are logical materials for use herein. Such materials include Class I active substances defined by the U.S. Food and Drug Administration (FDA) tentative final monograph for human over-the-counter medicinal skin protectant drug products (21 CFR §347), which currently include: allantoin, aluminum hydroxide gel, calamine, cocoa butter, polydimethylsiloxane, cod liver oil (combination), glycerin, kaolin, petrolatum, lanolin, mineral oil, shark liver oil, white petrolatum, talc, topical starch, zinc acetate, zinc carbonate, zinc oxide, etc. Other possible materials are Class DI active substances defined by the tentative final monograph (21 C.FR §347) of the U.S. Food and Drug Administration's human non-prescription medicinal skin protectant drug product, which currently includes: live yeast cell derivatives, aluminum allantoin, aluminum acetate, microporous cellulose, cholecalciferol, colloidal oatmeal, cysteine hydrochloride, dexpanthenol, Peru balsam oil, protein hydrolyzate, racemic methionine, sodium bicarbonate, vitamin A, a buffered mixture of cation and anion exchange resins, corn starch, triethanolamine, etc. In addition, other possible materials are Class II active substances defined by the tentative final monograph (21 C.FR §347) of the U.S. Food and Drug Administration's human non-prescription medicinal skin protectant drug product, which includes: bismuth subnitrate, boric acid, ferric chloride, polyvinyl pyrrolidone-vinyl acetate copolymer, sulfur, tannic acid, etc. The skin care agent can be selected from these materials and their mixtures. As mentioned above, the materials used should be safe. The rheological solid personal care composition may comprise between about 0.001 wt. % and about 20 wt. % of the skin care agent, based on the weight of the rheological solid personal care composition. The concentration range of the skin care agent in the composition varies from material to material.
[0088] Hair treatment actives
[0089] Pyridinethione anti-dandruff particles, especially 1-hydroxy-2-pyridinethione salts, are suitable particulate anti-dandruff agents. Based on the total weight of the composition, the concentration of pyridinethione anti-dandruff particles is typically in the range of about 0.01% by weight to about 5% by weight, generally about 0.1% by weight to about 3% by weight, usually about 0.1% by weight to about 2% by weight. Suitable pyridinethione salts include those formed by heavy metals such as zinc, tin, cadmium, magnesium, aluminum and zirconium, generally zinc, typically zinc salts of 1-hydroxy-2-pyridinethione (referred to as "zinc pyridinethione" or "ZPT"), and 1-hydroxy-2-pyridinethione salts, usually in the form of flaky particles, wherein the particles have an average size of up to about 20 μm, typically up to about 5 μm, and usually up to about 2.5 μm. Salts formed by other cations such as sodium may also be suitable. Pyridinethione antidandruff agents are described, for example, in U.S. Patent 2,809,971; U.S. Patent 3,236,733; U.S. Patent 3,753,196; U.S. Patent 3,761,418; U.S. Patent 4,345,080; U.S. Patent 4,323,683; U.S. Patent 4,379,753; and U.S. Patent 4,470,982. As noted above, ZPT is the preferred pyridinethione salt.
[0090] In addition to the anti-dandruff active, the composition may contain one or more antifungal or antimicrobial actives in addition to the metal pyrithione salt active. Suitable antimicrobial actives include coal tar, sulfur, charcoal, Whitefield's ointment, castellani's pigment, aluminum chloride, gentian violet, octopirox (octopirox olamine), cyproterone hydroxyethylamine, undecylenic acid and its metal salts, potassium permanganate, selenium sulfide, sodium thiosulfate, propylene glycol, bitter orange oil, urea preparations, griseofulvin, 8-hydroxyquinoline clioquinol, thiodibutazole, thiocarbamates, haloprogin, polyenes, hydroxypyridone, morpholine, benzylamine, allylamines (such as terbinafine), tea tree oil, clove leaf oil, coriander, palmarosa, berberine, thyme red, cinnamon oil, cinnamaldehyde, citronellal, cynarin, sulfonated shale oil, Sensiva SC-50, Elestab HP-100, azelaic acid, lysozyme, iodopropynyl butylcarbamate (IPBC), isothiazolinones such as octylisothiazolinone and azoles, and combinations thereof. Typical antimicrobial agents include itraconazole, ketoconazole, selenium sulfide, and coal tar.
[0091] Underarm handling of active substances
[0092] The rheological solid personal care composition may contain from about 0.1 wt. % to about 50 wt. %, based on the weight of the rheological solid personal care composition, of a soluble antiperspirant active suitable for application to human skin. The concentration of the antiperspirant active in the composition should be sufficient to provide the desired sweat wetness and odor control to the finished antiperspirant.
[0093] The rheological solid personal care composition may comprise, or provide a finished product comprising, a soluble antiperspirant active in a concentration of from about 0.1 wt % to about 35 wt %, preferably from about 3 wt % to about 20 wt %, even more preferably from about 4 wt % to about 19 wt %, based on the weight of the composition. All of these weight percentages are calculated on an anhydrous metal salt basis, excluding water and any complexing agents or buffers, such as glycine, glycinate or other complexing agents or buffers.
[0094] Soluble antiperspirant actives for use in the compositions of the present invention include any compound, composition or other material having antiperspirant activity. Preferred antiperspirant actives include astringent metal salts, especially inorganic and organic salts of aluminum, zirconium and zinc, and mixtures thereof. Particularly preferred are aluminum and zirconium salts, such as aluminum halides, aluminum chlorohydrates, aluminum hydroxyhalides, zirconium oxyhalides, zirconium oxyhalides and mixtures thereof.
[0095] Preferred aluminum salts for use in antiperspirant compositions include those conforming to the following formula:
[0096] Al2(OH) a Cl b ·x H2O
[0097] wherein a is from about 2 to about 5; the sum of a and b is about 6; x is from about 1 to about 6; and wherein a, b and x may have non-integer values. Particularly preferred is aluminum hydroxychloride, wherein a=5 is referred to as "5 / 6 basic aluminum hydroxychloride", and wherein a=4 is referred to as "2 / 3 basic aluminum hydroxychloride".
[0098] Preferred zirconium salts for use in antiperspirant compositions include those conforming to the following formula:
[0099] ZrO(OH) 2-a Cl a ·x H2O
[0100] wherein a is any number having a value from about 0 to about 2; x is from about 1 to about 7; and wherein both a and x may have non-integer values. Particularly preferred zirconium salts are those complexes that also contain aluminum and glycine, commonly referred to as ZAG complexes. These ZAG complexes contain aluminum hydroxychloride and zirconium hydroxychloride conforming to the above formula.
[0101] Active substances for tooth treatment
[0102] The composition may include a water-soluble fluoride in an amount sufficient to provide a fluoride ion concentration of about 0.0025% to about 5.0%, preferably about 0.005% to about 2.0% by weight in the composition and / or when used, thereby providing an anti-caries effect. A variety of fluoride ion-generating materials can be used as soluble fluoride sources in the composition of the present invention. Examples of suitable fluoride ion-generating materials can be found in U.S. Pat. No. 3,535,421, issued to Briner et al. on October 20, 1970, and U.S. Pat. No. 3,678,154, issued to Widder et al. on July 18, 1972. Representative fluoride ion sources include stannous fluoride, sodium fluoride, potassium fluoride, sodium monofluorophosphate, indium fluoride, and the like. Stannous fluoride and sodium fluoride and mixtures thereof are preferred.
[0103] Active ingredients for external use
[0104] The rheological solid personal care composition may include insoluble topical active substances. In some aspects, the rheological solid personal care composition may include about 0.01 wt % to about 20 wt %, alternatively about 0.025 wt % to about 10 wt %, alternatively about 0.1 wt % to about 7 wt %, alternatively about 0.25 wt % to about 5 wt %, alternatively about 1 wt % to about 3 wt % topical active substances, all percentages are by the weight of the rheological solid personal care composition. Non-limiting examples of topical active substances may include analgesics such as methyl salicylate, ibuprofen and diclofenac sodium, melatonin, capsaicin, capsicum, camphor, menthol, anesthetics such as benzocaine, corticosteroids such as hydrocortisone and hydrocortisone acetate, and combinations thereof.
[0105] Water Phase
[0106] Rheological solid personal care compositions contain a large amount of water. However, other components can be optionally dissolved in water to form an aqueous phase. These components are referred to as soluble active agents. Such soluble active agents may include, but are not limited to, catalysts, activators, peroxides, enzymes, antimicrobial agents, preservatives, salts (such as sodium chloride), polyols, soluble pharmaceutical active substances, and combinations thereof. Crystallizing agents and insoluble active agents are dispersed in the aqueous phase. Suspending agents may be dissolved in the aqueous phase (as with gums and other soluble polymers) or may be dispersed in the aqueous phase (as with clay particles).
[0107] catalyst
[0108] In some aspects, the soluble active agent may include one or more metal catalysts. In some aspects, the metal catalyst may include one or more of the following: dichloro-1,4-diethyl-1,4,8,11-tetraazabicyclo[6.6.2]hexadecanemanganese(II); and dichloro-1,4-dimethyl-1,4,8,11-tetraazabicyclo[6.6.2]hexadecanemanganese(II). In some aspects, the non-metal catalyst may include one or more of the following: 2-[3-[(2-hexyldodecyl)oxy]-2-(sulfoxy)propyl]-3,4-dihydroisoquinolinium, inner salt; 3,4-dihydro-2-[3-[(2-pentylundecyl)oxy]-2-(sulfoxy)propyl]isoquinolinium, inner salt; 2-[3-[(2-butyldecyl)oxy]-2-(sulfoxy)propyl]-3,4-dihydro Isoquinolinium, inner salt; 3,4-dihydro-2-[3-(octadecyloxy)-2-(sulfooxy)propyl]isoquinolinium, inner salt; 2-[3-(hexadecyloxy)-2-(sulfooxy)propyl]-3,4-dihydroisoquinolinium, inner salt; 3,4-dihydro-2-[2-(sulfooxy)-3-(tetradecyloxy)propyl]isoquinolinium, inner salt; 2-[3-(dodecyloxy)-2-(sulfooxy)propyl]-3,4- Dihydroisoquinolinium, inner salt; 2-[3-[(3-hexyldecyl)oxy]-2-(sulfooxy)propyl]-3,4-dihydroisoquinolinium, inner salt; 3,4-dihydro-2-[3-[(2-pentylnonyl)oxy]-2-(sulfooxy)propyl]isoquinolinium, inner salt; 3,4-dihydro-2-[3-[(2-propylheptyl)oxy]-2-(sulfooxy)propyl]isoquinolinium, inner salt; 2-[3-[(2-butyl 2-[3-(decyloxy)-2-(sulfooxy)propyl]-3,4-dihydroisoquinolinium, inner salt; 3,4-dihydro-2-[3-(octyloxy)-2-(sulfooxy)propyl]isoquinolinium, inner salt; and 2-[3-[(2-ethylhexyl)oxy]-2-(sulfooxy)propyl]-3,4-dihydroisoquinolinium, inner salt.
[0109] Activator
[0110] In some aspects, the soluble active agent may include one or more activators. In some aspects, the activator may include one or more of the following: tetraacetylethylenediamine (TAED); benzoyl caprolactam (BzCL); 4-nitrobenzoyl caprolactam; 3-chlorobenzoyl caprolactam; benzoyloxybenzene sulfonate (BOBS); nonanoyloxybenzene sulfonate (NOBS); phenyl benzoate (PhBz); decanoyloxybenzene sulfonate (C 10-OBS); benzoyl valerolactam (BZVL); octanoyloxybenzenesulfonate (C8-OBS); perhydrolyzable esters; 4-[N-(nonanoyl)aminocaproyloxy]-benzenesulfonic acid sodium salt (NACA-OBS); dodecanoyloxybenzenesulfonate (LOBS or C 12 -OBS); 10-undecenoyloxybenzenesulfonate (UDOBS or C with unsaturation at position 10); 11 -OBS); decanoyloxybenzoic acid (DOBA); (6-octanoylaminohexanoyl)oxybenzenesulfonate; (6-nonanoylaminohexanoyl)oxybenzenesulfonate; and (6-decanoylaminohexanoyl)oxybenzenesulfonate.
[0111] Peroxycarboxylic acid
[0112] In some aspects, the soluble active agent may comprise one or more preformed peroxycarboxylic acids. In some aspects, the peroxycarboxylic acid may comprise one or more of the following: peroxymonosulfuric acid; perimidic acid; percarbonic acid; percarboxylic acid and salts of said acid; phthalimidoperoxycaproic acid; aminoperoxyacid; 1,12-diperoxydodecanedioic acid; and monoperoxyphthalic acid (hexahydrated magnesium salt), wherein the aminoperoxyacid may comprise N,N'-terephthaloyl-bis(6-aminocaproic acid), monononanamide of peroxysuccinic acid (NAPSA) or peroxyadipic acid (NAPAA), or N-nonanoylaminoperoxycaproic acid (NAPCA).
[0113] In some aspects, the water-based and / or water-soluble benefit agent may include one or more diacyl peroxides. In some aspects, the diacyl peroxide may include one or more of dinonanoyl peroxide, didecanoyl peroxide, didecanoyl peroxide, diundecanoyl peroxide, dilauroyl peroxide and dibenzoyl peroxide, di-(3,5,5-trimethylhexanoyl) peroxide, wherein the diacyl peroxide may be clathrate.
[0114] peroxide
[0115] In some aspects, the soluble active agent may include one or more hydrogen peroxides. In some aspects, the hydrogen peroxide source may include one or more of perborates, percarbonates, peroxyhydrates, peroxides, persulfates, and mixtures thereof, in one aspect, the hydrogen peroxide source may include sodium perborate, in one aspect, the sodium perborate may include monohydrate or tetrahydrate, sodium pyrophosphate peroxyhydrate, urea peroxyhydrate, trisodium phosphate peroxyhydrate, and sodium peroxide.
[0116] Enzymes
[0117] In some aspects, the soluble active agent may comprise one or more enzymes. In some aspects, the enzyme may comprise one or more of the following: peroxidase, protease, lipase, phospholipase, cellulase, cellobiohydrolase, cellobiose dehydrogenase, esterase, cutinase, pectinase, mannanase, pectate lyase, keratinase, reductase, oxidase, phenoloxidase, lipoxygenase, ligninase, pullulanase, tannase, pentosanases, glucanase, arabinosidase, hyaluronidase, chondroitinase, laccase, amylase, DNA enzyme and combinations thereof.
[0118] Sensate
[0119] In some aspects, the soluble active agent may include one or more components that provide sensory benefits, commonly referred to as sensory agents. Sensory agents may have sensory attributes, such as warmth, tingling or coolness. Suitable sensory agents include, for example, menthol, menthyl lactate, leaf alcohol, camphor, clove bud oil, eucalyptus oil, anethole, methyl salicylate, eucalyptol, cinnamon, 1-8 menthyl acetate, eugenol, oxanone, α-ionone, propenyl ethyl guaiacol, thymol, linalool, benzaldehyde, the cinnamaldehyde glycerol acetal called "CGA", the N-[(ethoxycarbonyl) methyl)-p-menthane-3-carboxamide called "WS-5" supplied by Renessenz-Symrise and mixtures thereof.
[0120] In some aspects, the sensate comprises a cooling agent. The cooling agent can be any of a variety of substances. Included in the present invention are amides, menthols, ketals, diols, and mixtures thereof. Some examples of amide cooling agents include, for example, p-menthane aminocarboxamide agents such as N-ethyl-p-menthane-3-carboxamide (commercially known as "WS-3"), N,2,3-trimethyl-2-isopropylbutanamide (known as "WS-23"), and N-(4-cyanomethylphenyl)-p-menthanecarboxamide (known as G-180 and supplied by Givaudan). G-180 is typically provided as a 7.5% solution in a flavor oil such as spearmint oil or peppermint oil. Examples of menthol cooling agents include, for example, menthol; 3-1-menthoxypropane-1,2-diol known as TK-10 and manufactured by Takasago; menthone glycerol acetal known as "MGA" and manufactured by Haarmann and Reimer; and menthone glycerol acetal known as and menthyl lactate manufactured by Haarmann and Reimer. As used herein, the terms menthol and menthyl include both the dextrorotatory and levorotatory isomers of these compounds as well as their racemic mixtures.
[0121] In some aspects, the sensate comprises a cooling agent selected from the group consisting of: menthol; 3-1-menthoxypropane-1,2-diol; menthyl lactate; N,2,3-trimethyl-2-isopropylbutyramide; N-ethyl-p-menthane-3-carboxamide; N-(4-cyanomethylphenyl)-p-menthanecarboxamide; ethylamino oxalate menthyl; and combinations thereof. In some aspects, the sensate comprises menthol; N,2,3-trimethyl-2-isopropylbutyramide; N-(4-cyanomethylphenyl)-p-menthanecarboxamide; ethylamino oxalate menthyl; and combinations thereof.
[0122] In some aspects, the sensate comprises a warming sensate. Non-limiting examples of warming sensates may include vanillyl alcohol n-butyl ether (sold by Takasago International under the trade name TK-1000), vanillyl alcohol butyl ether (sold by Takasago International under the trade name (commercially available from Corum, Inc., Taipei, Taiwan, China), capsaicin, nolvadenin, ginger, chili pepper (available under the trade name Capsicum LC481 is commercially available from Gattefossé, Lyon, France), and combinations thereof.
[0123] In some aspects, the sensate comprises a tingling sensate. Non-limiting examples of tingling sensates can include Zanthoxylum bungeanum, hydroxy-alpha sanshool, spiky nut extract, spilanthol, and combinations thereof. Suitable sensory enhancers can include a neurosoothing agent, such as Mariliance available from Givaudan (Vernier, Switzerland). TM .
[0124] One advantage of including sensates is that they can provide a topical sensory effect. When a rheological solid personal care composition having one or more sensates is applied to the skin, it can provide a feel on the skin that can work in tandem with the scent to provide an enhanced perception of product strength.
[0125] The rheological solid personal care composition may comprise from about 0.001 wt. % to about 1.5 wt. %, alternatively from about 0.01 wt. % to about 1 wt. %, alternatively from about 0.1 wt. % to about 0.75 wt. %, alternatively from about 0.2 wt. % to about 0.5 wt. % of a sensate, all percentages being by weight of the rheological solid personal care composition.
[0126] Surfactants
[0127] In some aspects, the soluble active agent may comprise one or more surfactants. These include cationic, anionic and non-surfactants. This includes fabric conditioning softener surfactants and cleaning surfactants.
[0128] Antimicrobial compounds
[0129] In some aspects, the soluble active agent may include an effective amount of compounds for reducing the number of live microorganisms in the air or on an inanimate surface. Antimicrobial compounds are effective for gram-negative or gram-positive bacteria or fungi that are usually present on indoor surfaces such as sofas, pillows, pet bedding and carpets that contact human skin or pets. Such microbial strains include Klebsiella pneumoniae, Staphylococcus aureus, Aspergillus niger, Klebsiella pneumoniae, Streptococcus pyogenes, Salmonella choleraesuis, Escherichia coli, Trichophyton mentagrophytes and Pseudomonas aeruginosa. Antimicrobial compounds are also able to effectively reduce the number of live viruses, such as H1-N1, rhinovirus, respiratory syncytial virus, polio virus type 1, rotavirus, influenza A virus, herpes simplex type 1 and 2, hepatitis A virus, and human coronavirus.
[0130] The antimicrobial compound suitable for the rheological solid composition can be any organic material that does not cause damage to the appearance of the fabric (e.g., discoloration, coloration such as yellowing, bleaching). Water-soluble antimicrobial compounds include organic sulfur compounds, halogenated compounds, cyclic organic nitrogen compounds, low molecular weight aldehydes, quaternary compounds, dehydroacetic acid, phenyl and phenoxy compounds or mixtures thereof.
[0131] Quaternary compounds may be used. Examples of commercially available quaternary compounds suitable for use in the rheological solid composition are available from Lonza Corporation. And the product name 2250 was a didecyldimethylammonium chloride quaternary compound available from Lonza Corporation.
[0132] The antimicrobial compound may be present in an amount from about 500 ppm to about 7000 ppm, alternatively from about 1000 ppm to about 5000 ppm, alternatively from about 1000 ppm to about 3000 ppm, alternatively from about 1400 ppm to about 2500 ppm by weight of the rheological solid personal care composition.
[0133] preservative
[0134] In some aspects, the soluble active agent may include a preservative. The preservative may be present in an amount sufficient to prevent spoilage or prevent the growth of inadvertently added microorganisms for a specific period of time, but not sufficient to contribute to the odor neutralization properties of the rheological solid composition. In other words, the preservative is not used as an antimicrobial compound to kill microorganisms on the surface on which the rheological solid composition is deposited, thereby eliminating odors produced by the microorganisms. Instead, it is used to prevent spoilage of the rheological solid personal care composition to extend the shelf life of the rheological solid personal care composition.
[0135] The preservative can be any organic preservative material that does not cause damage to the appearance of the fabric (e.g., discoloration, coloring, bleaching). Suitable water-soluble preservatives include organic sulfur compounds, halogenated compounds, cyclic organic nitrogen compounds, low molecular weight aldehydes, parabens, propylene glycol materials, isothiazolinones, quaternary compounds, benzoates, low molecular weight alcohols, dehydroacetic acid, phenyl and phenoxy compounds or mixtures thereof.
[0136] A non-limiting example of a commercially available water-soluble preservative includes a mixture of about 77% 5-chloro-2-methyl-4-isothiazolin-3-one and about 23% 2-methyl-4-isothiazolin-3-one sold by Rohm and Haas Co. under the trade name CG is a broad-spectrum preservative sold as a 1.5% aqueous solution; 5-bromo-5-nitro-1,3-dioxane, which is sold under the trade name Bronidox Available from Henkel; 2-bromo-2-nitropropane-1,3-diol, which is sold under the trade name Available from Inolex; 1,1'-hexamethylenebis(5-(p-chlorophenyl)biguanide) (commonly known as chlorhexidine) and its salts, such as those with acetic acid and digluconic acid; a 95:5 mixture of 1,3-bis(hydroxymethyl)-5,5-dimethyl-2,4-imidazolidinedione and 3-butyl-2-iodopropynylcarbamate, which is sold under the trade name Glydant Available from Lonza; N-[1,3-bis(hydroxymethyl)2,5-dioxo-4-imidazolidinyl]-N,N'-bis(hydroxy-methyl)urea, which is commonly known as diazolidinyl urea and sold under the trade name II was purchased from Sutton Laboratories, Inc.; N,N"-methylenebis{N'-[1-(hydroxymethyl)-2,5-dioxo-4-imidazolidinyl]urea}, which is commonly known as imidazolidinyl urea, for example, under the trade name Available from 3V-sigma under the trade name Unicide Purchased from Induchem under the trade name Ger-mall Available from Sutton Laboratories, Inc.; polymethoxybicyclic oxazolidine, which is sold under the trade name C was purchased from Hüls America; formaldehyde; glutaraldehyde; polyaminopropyl biguanide, which is sold under the trade name Cosmocil Available from ICI Americas, Inc., or under the trade name Available from Brooks, Inc; dehydroacetic acid; and benzisothiazolinone, which is sold under the trade name Koralone TM B-119 was purchased from Rohm and Hass Corporation; 1,2-benzisothiazoline-3-one; Acticide MBS.
[0137] Suitable levels of preservatives are from about 0.0001 wt % to about 0.5 wt %, alternatively from about 0.0002 wt % to about 0.2 wt %, alternatively from about 0.0003 wt % to about 0.1 wt % by weight of the rheological solid personal care composition.
[0138] Rheological solid personal care composition can include aqueous carrier. The aqueous carrier used can be distilled water, deionized water or tap water. Water can exist in any amount so that the rheological solid personal care composition becomes an aqueous solution. Water can be about 85 wt % to 99.5 wt %, alternatively about 90 wt % to about 99.5 wt %, alternatively about 92 wt % to about 99.5 wt %, alternatively about 95 wt % by weight of the rheological solid personal care composition. Alternatively, water can be about 55 wt % to about 99.5 wt %, alternatively about 60 wt % to about 99.5 wt %, alternatively about 65 wt % to about 95 wt %, alternatively about 70 wt % to about 95 wt %, alternatively about 75 wt % to about 90 wt % by weight, and all percentages are by the weight of the rheological solid personal care composition.
[0139] Water containing small amounts of low molecular weight monoalcohols (e.g., ethanol, methanol, and isopropanol) or polyols (such as ethylene glycol and propylene glycol) may also be used. However, volatile low molecular weight monoalcohols such as ethanol and / or isopropanol should be limited because these volatile organic compounds will cause flammability problems and environmental pollution problems. If a small amount of low molecular weight monoalcohols is present in the rheological solid composition (due to the addition of these alcohols to such materials as fragrances or as stabilizers for some preservatives), the content of the monoalcohols may be from about 1% to about 5% by weight, alternatively less than about 6% by weight, alternatively less than about 3% by weight, alternatively less than about 1% by weight, based on the weight of the rheological solid personal care composition.
[0140] Adjuvant
[0141] Adjuvants may be added to the rheological solid personal care compositions herein for their known purposes. Such adjuvants include, but are not limited to, water-soluble metal salts, including zinc salts, copper salts, and mixtures thereof; antistatic agents; insect and moth repellents; colorants; antioxidants; aromatherapeutic agents, and mixtures thereof.
[0142] The composition of the present invention may also contain any additives commonly used in the field under study. For example, unencapsulated pigments, film formers, dispersants, antioxidants, essential oils, preservatives, fragrances, fat-soluble polymers dispersible in a medium, fillers, neutralizers, silicone elastomers, cosmetic and skin care oil-soluble active agents such as emollients, moisturizers, vitamins, anti-wrinkle agents, essential fatty acids, sunscreens, and mixtures thereof may be added.
[0143] Solvents
[0144] The rheological solid personal care composition may include a solvent. Non-limiting examples of solvents may include ethanol, glycerol, propylene glycol, polyethylene glycol 400, polyethylene glycol 200, and mixtures thereof. In some aspects, the rheological solid personal care composition may include from about 0.5 wt % to about 15 wt % of a solvent, alternatively from about 1.0 wt % to about 10 wt % of a solvent, alternatively from about 1.0 wt % to about 8.0 wt % of a solvent, alternatively from about 1 wt % to about 5 wt % of a solvent, all percentages being based on the weight of the rheological solid personal care composition.
[0145] Vitamins
[0146] As used herein, "xanthine compound" means one or more xanthines, their derivatives, and mixtures thereof. Xanthine compounds that can be used herein include, but are not limited to, caffeine, xanthine, 1-methylxanthine, theophylline, theobromine, their derivatives, and mixtures thereof. Among these compounds, caffeine is preferred in view of the solubility of caffeine in the composition. The composition may contain by weight from about 0.05% by weight, preferably from about 2.0% by weight, more preferably from about 0.1% by weight, still more preferably from about 1.0% by weight, and to about 0.2% by weight, preferably to about 1.0% by weight, more preferably to about 0.3% by weight of xanthine compounds.
[0147] As used herein, "vitamin B3 compound" refers to one or more compounds having the formula:
[0148]
[0149] Wherein R is -CONH2 (ie nicotinamide), -COOH (ie nicotinic acid) or -CH2OH (ie nicotinic alcohol); their derivatives; their mixtures; and salts of any of the foregoing substances.
[0150] Exemplary derivatives of the aforementioned vitamin B3 compounds include nicotinic acid esters, including non-vasodilating nicotinic acid esters (e.g., tocopheryl nicotinate and myristyl nicotinate), nicotinyl amino acids, nicotinyl alcohol esters of carboxylic acids, nicotinic acid N-oxide, and nicotinamide N-oxide. The composition may contain from about 0.05 wt%, preferably from about 2.0 wt%, more preferably from about 0.1 wt%, still more preferably from about 1.0 wt%, and to about 0.1 wt%, preferably to about 0.5 wt%, more preferably to about 0.3 wt% of the vitamin B3 compound by weight.
[0151] As used herein, the term "panthenol compound" is broad enough to include panthenol, one or more pantothenic acid derivatives, and mixtures thereof. Panthenol and its derivatives may include D-panthenol ([R]-2,4-dihydroxy-N-[3-hydroxypropyl]-3,3-dimethylbutyramide), DL-panthenol, pantothenic acid and its salts (preferably calcium salts), panthenol triacetate, royal jelly, pantethine, panthenylthioethylamine, panthenyl ethyl ether, pancreatic acid, pantothenic acid lactose, vitamin B complexes, or mixtures thereof. The composition may contain from about 0.01% by weight, preferably from about 0.02% by weight, more preferably from about 0.05% by weight, and to about 3% by weight, preferably to about 1% by weight, more preferably to about 0.5% by weight of a panthenol compound.
[0152] Salt
[0153] In some aspects, the rheological solid personal care composition may include a salt that contributes to thermal stability. Non-limiting examples of salts may include sodium chloride, sodium sulfate, and combinations thereof. In some aspects, the rheological solid personal care composition may include from about 0.1 wt % to about 10 wt %, alternatively from about 1 wt % to about 7 wt %, alternatively from 3 wt % to about 5 wt % of the salt, all percentages being by weight of the rheological solid personal care composition.
[0154] Soluble pharmaceutical active substances
[0155] The rheological solid personal care composition may include a soluble pharmaceutical active. In some aspects, the rheological solid personal care composition may include from about 0.1% to about 5% by weight, alternatively from about 0.25% to about 3% by weight, alternatively from 0.5% to about 1.5% by weight of a soluble pharmaceutical active, all percentages being by weight of the rheological solid personal care composition. Non-limiting examples of soluble pharmaceutical actives may include antihistamines such as diphenhydramine hydrochloride and tripeliramine hydrochloride, anesthetics such as lidocaine hydrochloride, dibucaine, pramoxine and tetracaine, and combinations thereof.
[0156] Consumer Products / Rheological Solid Personal Care Compositions
[0157] In one aspect, the rheological solid personal care composition can provide at least temporary suppression of coughing due to minor throat and bronchial irritation, such as that associated with a cold. In one aspect, the rheological solid personal care composition can provide at least temporary relief of minor aches and / or pains of muscles and / or joints. In one aspect, the rheological solid personal care composition can provide relief of nasal congestion.
[0158] The rheological solid personal care composition can be applied to the skin of the user's back, throat, forehead and / or chest. The user can place a desired amount of the rheological solid personal care composition on his or her skin and rub it therein for about 5 seconds to about 3 minutes, alternatively about 20 seconds to about 90 seconds, alternatively about 30 seconds to about 60 seconds. In one example, the rheological solid personal care composition can be covered with a warm dry cloth after being applied to the skin.
[0159] A dose of rheological solid personal care composition can be applied to the skin and / or clothing once a day, or twice a day, or three times a day. In one aspect, a dose of rheological solid personal care composition can be applied to the skin up to three times a day. The rheological solid personal care composition can be applied to the skin and / or clothing every day or only as needed. Preferably, the rheological solid personal care composition is applied to clothing or other objects and allowed to dry before contact with clothing or other objects. The rheological solid personal care composition is preferably applied to a desired area that is dry or dried before application.
[0160] A dose of the rheological solid personal care composition may contain from about 0.5 g to about 10 g, alternatively from about 1 g to about 8 g, alternatively from about 1.5 g to about 6 g, alternatively from about 3 g to about 4.5 g, alternatively about 7.5 g.
[0161] Another aspect of the present invention includes a method of providing one or more health benefits, beauty benefits, and / or consumer benefits by applying a rheological solid personal care composition to a user in need thereof. Non-limiting examples of one or more health benefits may include providing nasal congestion relief, suppressing cough, providing muscle aches and pain relief, improving the sleep quality of users suffering from colds or flu, providing local analgesia, providing relief of rashes, pain, and / or dermatitis, and combinations thereof. Non-limiting examples of one or more beauty benefits may include moisturizing, cleaning, beautifying, and combinations thereof. Non-limiting examples of one or more consumer benefits may include providing soothing steam, providing aromatherapy, promoting sleep, providing stress relief, empowering, providing calming and / or relaxing fragrance, and combinations thereof.
[0162] The compositions of the present invention can achieve excellent consumer aesthetics without compromising stability. The above preferred ratios and weight percentages provide adequate medium coverage of the product without feeling dry or flaky and provide a good smoothing / evening effect on the skin. They also provide a pleasant fresh feeling on the skin when the composition is applied.
[0163] The present invention also contemplates kits and / or pre-packaged materials suitable for consumer use comprising one or more compositions according to the description herein. The packaging and application devices for any subject matter of the present invention can be selected and manufactured by a person skilled in the art based on their general knowledge; and adjusted according to the nature of the composition to be packaged. In practice, the type of device used may be specifically related to the consistency of the composition, in particular its viscosity; it may also depend on the nature of the components present in the composition, such as the presence of volatile compounds.
[0164] Given the soft solid nature of the material, the rheological solid personal care compositions of the present invention may also be combined with devices such as containers, nonwoven sheets or rollers. Such composition / device combinations may be used as consumer products in various applications such as skin cooling or steam applicators (e.g., sticks, balls), nonwoven webs (e.g., surface wipes, mops, toilet paper), and fabric enhancements (e.g., fabric dryer sheets, fabric stain removal, fabric wrinkle reduction, fabric softeners).
[0165] characteristic
[0166] Phase stability
[0167] As used herein, phase stability is a measure of the effectiveness of a suspending agent in preventing the sedimentation or creaming of dispersed active particles. A hot mixture of a crystallizing agent dissolved in water at processing temperature has a viscosity of about several millipascal seconds. At this stage, active substances are added and dispersed in the mixture as particles. In the time before the crystallizing agent crystallizes, the active particles tend to cream (i.e. rise) or settle (i.e. settle), resulting in unacceptable material separation for consumers. Suspending agents prevent the dispersed active particles from being separated as a whole during the crystallization process, and allow the mesh of fibrous crystalline particles to entrain the dispersed active particles. Without being bound by theory, it is believed that suspending agents increase the viscosity of the suspension or give the mixture a yield stress that prevents the separation of active particles. A phase stability value of "0" is not preferred, a value of "1" is a preferred value, and a value of "2" is most preferred. Phase stability is determined using the phase stability test method described below.
[0168] Stability Temperature
[0169] As used herein, the stability temperature is the temperature at which most or all of the crystallization agent is completely dissolved in the aqueous phase so that the composition no longer exhibits a stable solid structure and can also be considered a liquid. In some aspects, the minimum stability temperature can be from about 30°C to about 95°C, from about 40°C to about 90°C, from about 50°C to about 80°C, or from about 60°C to about 70°C, as these temperatures are typical in the supply chain. The stability temperature can be determined using the thermal stability test method described below.
[0170] Firmness
[0171] According to the expected application, such as rods, the firmness of the composition can also be considered. The firmness of the composition can be expressed, for example, in Newton force. For example, the present composition comprising 1% by weight-3% by weight of crystallizing agent can give a value of about 4 to 12N in the form of a coating on a solid rod or sheet. It is apparent that the firmness of the composition according to an embodiment of the present invention can, for example, make the composition advantageously self-supporting and can easily release liquid and / or active substances to form a satisfactory deposit on the surface, such as skin and / or body surface growths such as keratinous fibers. In addition, this firmness can give the present composition good impact strength, and the composition can be molded or cast into, for example, rod-shaped or sheet-like forms, such as wipes or dryer paper products. The rheological solid personal care composition can also be transparent or clear, including, for example, a composition without pigment. The preferred firmness is between about 0.1 N and about 50.0 N, more preferably between about 0.5 N and about 40.0 N, more preferably between about 1.0 N and about 30.0 N, and most preferably between about 2.5 N and about 15.0 N. Firmness can be measured using the Firmness Test Method, as described below.
[0172] Liquid Extrusion
[0173] Depending on the intended application, such as a stick, liquid extrusion of the composition may also be considered. This is a measure of the amount of work required per unit volume when squeezing water out of the composition, with the greater the value, the more difficult it is to squeeze out the water. For example, when the composition is applied to the skin, a low value may be preferred. For example, when applied to a substrate that requires a "dry to touch but wet to wipe" property, a high value may be preferred. Preferred values are between about 100 J m-3 and about 6000 J m-3, alternatively between about 100 J m-3 and about 3000 J m-3, alternatively between about 300 J m-3 and about 2000 J m-3, alternatively between about 500 J m-3 and about 1500 J m-3. Liquid extrusion can be measured using a water extrusion test method, as described herein.
[0174] Solidity test method
[0175] All samples and processes were maintained at room temperature (25 ± 3°C) prior to and during testing, with care taken to ensure little or no water loss.
[0176] All measurements were performed using a TA-XT2 texture analyzer (Texture Technology Corporation, Scarsdale, NY, USA) equipped with a standard 45° angle penetration cone tool (Texture Technology Corp., part number TA-15).
[0177] To operate the TA-XT2 Texture Analyzer, attach the tool to the probe carrying arm and clean it with a low-lint wipe. The sample is positioned and held firmly so that the tool will contact a representative area of the sample. Reset the tool approximately 1 cm above the product sample.
[0178] Reposition the sample so that the tool will contact a second representative area of the sample. Perform a run by moving the tool precisely 10 mm into the sample at a rate of 2 mm / second. The "Run" button on the texture analyzer can be pressed to perform the measurement. Perform a second run by the same process on another representative area of the sample, at a sufficient distance from the previous measurement (they will not affect the second run). Perform a third run by the same process on another representative area of the sample, at a sufficient distance from the previous measurement (they will not affect the third run).
[0179] The following solidity values are returned from this measurement:
[0180] If the mixture does not completely crystallize at room temperature (e.g., remains clear or mushy), a value of "Not Solid" is returned; if the mixture exceeds 48N and is too hard to measure, a value of "Too Hard" is returned; otherwise, a value is returned that is the average of the maximum values of three measurements.
[0181] Thermal stability test method
[0182] Before testing, all samples and processes were kept at room temperature (25±3℃).
[0183] Sampling was done in two steps at a representative area on the sample. First, a small square hole about 5 mm deep was made by cleaning the scraper with a lab wipe and removing and discarding a small amount of sample from the top of the sample at that area. Second, the scraper was cleaned again with a clean lab wipe and a small amount of sample was collected from the square hole and loaded into the DSC pan.
[0184] Load the sample into the DSC pan. All measurements were performed in a high capacity stainless steel pan set (TA part number 900825.902). The pan, lid, and gasket were weighed and tared on a Mettler Toledo MT5 analytical microbalance (or equivalent). According to the manufacturer's instructions, the sample was loaded into the pan with a target weight of 20 mg (+ / - 10 mg), taking care to ensure that the sample was in contact with the bottom of the pan. The pan was then sealed with a TA high capacity die set (TA part number 901608.905). The final assembly was measured to obtain the sample weight.
[0185] The samples were loaded into a TA Q Series DSC according to the manufacturer's instructions. The DSC program used the following settings: 1) equilibrate at 25°C; 2) mark the end of cycle 1; 3) ramp to 90.00°C at 1.00°C / min; 4) mark the end of cycle 3; then 5) end of method; click Run.
[0186] The stability temperature is determined as the maximum peak of the highest temperature peaks. If the stability temperature cannot be measured because the sample is liquid or the thermal stability is too low / too high, the sample is assigned a "NM" value.
[0187] Water squeeze out test method
[0188] Before testing, all samples and processes were kept at room temperature (25±3℃).
[0189] The measurements to determine water squeeze-out were performed using a TA Discovery HR-2 hybrid rheometer (TA Instruments, New Castle, Delaware, USA) and the accompanying TRIOS software version 3.2.0.3877 or equivalent. The instrument was equipped with a DHR fixture unit (TA Instrument) and a 50 mm flat steel plate (TA Instrument). Calibration was performed according to the manufacturer's recommendations, with particular attention paid to measuring the bottom of the DHR fixture unit to ensure that it was determined to be gap = 0.
[0190] Samples are prepared according to the embodiment process.It is important to prepare samples in Speed Mixer containers (Flak-Tech, Max 60 translucent cups, catalog number 501222t) so that the diameter of the sample matches the diameter of the HR-2 fixed unit.By running a thin scraper between the edge of the container and the sample, the sample is released from the container.The container is gently turned over and placed on a flat surface.Force is gently applied to the center of the bottom of the container that is turned over until the sample is released and gently slides out of the container.The sample is carefully placed in the center ring of the DHR fixed unit.Carefully ensure that the sample is not deformed and reshaped during the whole process.The diameter of the sample should be slightly smaller than the inner diameter of the ring.This ensures that the force applied to the sample in the subsequent steps will not significantly deform the cylindrical shape of the sample, but allows the fluid to escape through the bottom of the sample.This also ensures that any change in the height of the sample for the experiment is equal to the amount of the water phase squeezed out during the test.At the end of the measurement, it should be confirmed by looking for water in the outflow tube connected to the fixed unit that the water phase is indeed squeezed out from the sample by measurement.If the water phase is not observed, it is considered that the sample does not squeeze out water and is not creative.
[0191] Set the instrument settings as follows. Select the axial test geometry. Then, set the "Geometry" options: Diameter = 50 mm; Gap = 45000 um; Loading Gap = 45000 um; Trim Gap Offset = 50 um; Material = "Steel"; Environmental System = "Peltier Plate". Set the "Process" options: Temperature = 25°C; Absorption Time = 0 seconds; Duration = 2000 seconds; Motor Direction = "Compression"; Constant Linear Rate = 2um sec-1; Maximum Gap Change = 0um; Torque = 0uN·m; Data Acquisition = "Save Image" every 5 seconds.
[0192] Manually move the steel tool within about 1000um of the sample surface, taking care that the tool does not touch the surface. In the Geometry options, reset the gap to this distance.
[0193] Start running.
[0194] The data are presented as two curves:
[0195] 1) Curve 1: axial force (N) on the left y-axis and step time (s) on the x-axis;
[0196] 2) Curve 2: gap (um) on the right y-axis and step time (s) on the x-axis.
[0197] The contact time - T(contact) is obtained from Curve 1. T(contact) is defined as the time the tool is in contact with the top of the sample. T(contact) is the step time when the first axial force data point exceeds 0.05N.
[0198] Sample thickness—L is the gap distance at the contact time and is expressed in meters.
[0199] Compression Time - T(compression) is the step time for a gap of 0.85*L or 15% of the sample.
[0200] The work required to squeeze water out of the structure is the area under the axial force curve between T (contact) and T (compression) in Figure 1 multiplied by the constant linear rate, or 2e-6m s-1 normalized by dividing by the total volume of the squeezed fluid and expressed in units of joules per cubic meter (Jm-3).
[0201] If water squeeze-out could not be measured because the sample was rheologically solid but too soft to handle for testing, the sample was assigned a "soft" value.
[0202] Phase stability test method
[0203] The samples were prepared according to the example procedure.
[0204] For the examples containing beads (Examples 1-6), the samples were divided into two parts, each part was placed in a container (Flak-Tech, Max 60 translucent cup, catalog number 501222t). The two containers were placed in an oven (Yamato, DKN 400; Yamato Scientific Co., Ltd., Tokyo, Japan, or equivalent) set at 60°C for one hour. The containers were then placed on a bench at room temperature (25°C ± 3°C). "Separation" in the sample describes creaming and / or sedimentation of the microspheres.
[0205] Each sample was visually inspected for phase stability and graded based on:
[0206] (Most preferred) If the composition appears stable with no discernible bead separation (i.e. homogeneous), a rating of "2" is given;
[0207] (Preferred) If the preparation appears to have no more than 25%
[0208] number of tracer beads, a grade of “1” is given;
[0209] • (Not preferred) If the composition appears unstable, as evidenced by almost complete separation with more than 75% of the number of beads at the top and bottom of the composition, a rating of "0" is given.
[0211] For the examples without beads (Examples 7-10), the entire sample was placed in a container (Flak-Tech, Max60 translucent cup, catalog number 501222t) and placed in an oven (Yamato, DKN 400; Yamato Scientific Co., Ltd., Tokyo, Japan, or equivalent) set at 60°C for one hour. The container was placed on a bench at room temperature (25±3°C). "Separation" in the sample describes creaming and / or sedimentation of insoluble active particles.
[0212] Each sample was visually inspected for phase stability and graded based on:
[0213] (Most preferred) A rating of "2" is given if the composition appears stable with no discernible or visual separation of insoluble active particles;
[0214] (Preferred) If the preparation appears to have only a few drops (estimated to be less than 25% by weight of the total amount of insoluble active agent added) on the top and / or bottom of the composition, a rating is given
[0215] "1". In some compositions, this can result in a "smooth" appearance on the surface;
[0216] (Not preferred) A rating of "0" is given if the composition appears unstable, as evidenced by nearly complete separation of the insoluble active agent (estimated to be less than 75% by weight of the total amount of insoluble active agent added) on either the top or bottom of the composition. For oil, this amount is sufficient to cause the oil to visually flow when the sample is turned sideways.
[0217] Example
[0218] Materials List
[0219] (1) Euxyl PE 9010 (EP) – Schülke & Mayr GmbH, Norderstedt, Germany, PE 9010 preservative, batch number 1501226
[0220] (2)SymDiol 68(S68)–Symrise,Holzminden,Germany, 68 preservatives, batch number 10300094
[0221] (3) Water - Millipore, Burlington, MA (18 m-ohm resistance)
[0222] (4) Sodium myristate NaM—TCI Chemicals, Cambridge, MA, catalog number M0483
[0223] (5) Xanthan gum (x-gum) – CPK, Denmark, Keltrol 1000, LOT 6J3749K
[0224] (6) Konjac gum (k-gum) - FMC Corporation, Philadelphia, PA,
[0225] XP 3464, FMC, lot number 1192605
[0226] (7) Probe particle microspheres – Cospheric LLC, Santa Barbra, CA, UVPMS-BG-1.00500-600um
[0227] (8) Sodium palmitate (NaP) - TCI Chemicals, Cambridge, MA, Catalog No. P0007
[0228] (9) Sodium stearate (NaS) - TCI Chemicals, Cambridge, MA, Catalog No. S0081
[0229] (10) Starch - Spectrum, New Brunswick, NJ, catalog number 9005-25-8
[0230] (11) Peppermint oil – MFR Ungerer, Bethlehem, PA, Lot No. 10059257SP-006
[0231] (12) Coconut Oil - Nature's Oil, Streetsboro, Ohio, Bulk Apothecary, SKU:
[0232] bna-513
[0233] (13) PMC–Encapsys, Wisconsin, USA, Heavenly Powder PA PMC Slurry, batch number: 201810456
[0234] (14) L-Menthol
[0235] (15) Nutmeg oil
[0236] (16) Camphor
[0237] (17) Eucalyptus Oil
[0238] (18) Cedar leaf oil FCC
[0239] (19) Rosin containing antioxidants
[0240] (20) Thymol NF
[0241] (21) Sodium chloride (NaCl) - VWR, catalog number BDH9286-500G
[0242] (22) Petroleum jelly - Calumet Specialty Products, Indianapolis, IN, catalog number PEN1722-00-C
[0243] (23) Glycerin - Alfa Aesar, catalog number A16205
[0244] (24) Rheocrysta c-2sp – Iwase Csofa USA Inc., Fort Lee, NJ, catalog number 7UA / 56203
[0245] (25) Synthetic hectorite suspension - Laponite XIG, BYK Additives & Instruments, Louisville, KY, catalog number 13-235
[0246] Original solution
[0247] (A1) Preparation of 1 wt% xanthan collagen stock solution (X-gum stock solution)
[0248] Into a Max 60 Speed Mixer cup (Flak-Tech, Max 60 translucent cup, catalog number 501222t), 0.202 g of Euxyl PE 9010 (1), 0.305 g of SymDiol 68 (2) and 49.007 g of water (3) were added. 0.502 g of xanthan gum (5) was added to the cup. The cup was placed in a Speed Mixer (Flak-Tech) at 2700 rpm for 150 seconds. The sample was allowed to stand for 2 hours and then mixed again in Speed Mixed at 2700 rpm for 150 seconds.
[0249] (A2) Preparation of 1 wt% Konjac Gum Stock Solution (K-gum Stock Solution)
[0250] Into a Max 60 Speed Mixer cup (Flak-Tech, Max 60 translucent cup, catalog number 501222t), 0.201 g of Euxyl PE 9010 (1), 0.301 g of SymDiol 68 (2), and 49.001 g of water (3) were added. 0.503 g of konjac gum (6) was added to the cup. The cup was placed in a Speed Mixer at 2700 rpm for 150 seconds. The sample was allowed to stand for 2 hours and then mixed again in the Speed Mixed at 2700 rpm for 150 seconds.
[0251] Example
[0252] Example 1
[0253] Samples A-AE used a suspending agent made from a gum blend to stabilize the suspended insoluble active particles ( Figure 4 In these compositions, the suspending agent consisted of varying amounts of x-gum and k-gum, accounting for 5% by weight of the crystallizing agent sodium myristate. Figure 4 The total weight of gum (i.e., x-gum weight + k-gum weight) is plotted along the x-axis, and the weight percentage of x-gum (i.e., x-gum weight / (x-gum weight + k-gum weight)) is plotted along the y-axis, where each point in the graph represents the phase stability results of the compositions in Tables 1-8 below. The "X" mark indicates a composition with a stability rating of "0" as determined by the Phase Stability Test Method, and is a comparative composition; the "" mark indicates a composition with a stability rating of "1" as determined by the Phase Stability Test Method, and is a preferred composition of the present invention; the "O" mark indicates a composition with a stability rating of "2" as determined by the Phase Stability Test Method, and is the most preferred composition. The data indicate that certain suspension compositions are more preferred for stabilizing insoluble active substances. Excluding the suspension agent from the composition always results in a stability rating of "0". Without being bound by theory, this is due to the presence of yield stress in the preparation formed by the suspension agent during the cooling process. Surprisingly, many compositional restrictions change significantly due to the presence of a crystallizing agent. Tables 1-8 also contain firmness (Firmness Test Method), temperature (Thermal Stability Test Method), and work (Hydroextrusion Test Method) data for representative comparative compositions and compositions of the present invention. These data demonstrate that the prototypes exhibit desirable properties for these rheologically solid personal care compositions, even in the presence of a suspending agent.
[0254] Preparation of composition
[0255] Compositions were prepared using a heated mixing apparatus. An overhead mixer (IKA Works Inc, Wilmington, NC, Model RW20 DMZ) and three-blade impeller design were assembled. All preparations were heated on a heating pad assembly (VWR, Radnor, PA, 7×7 CER Hotplate, Catalog No. NO97042-690) with heating controlled by an attached probe. All preparations were performed in 250 ml stainless steel beakers (Thermo Fischer Scientific, Waltham, MA).
[0256] Prepare the NaM / water solution by first adding the preservatives (1, 2). Then add water (3) and sodium myristate (4) to the beaker. Place the beaker on a heating pad assembly. Place an overhead stirrer in the beaker and set to rotate at 100 rpm. Set the heater to 80°C. Heat the preparation to 80°C. Turn off the heat and allow the preparation to cool to 60°C.
[0257] Final composition is prepared by adding 1% xanthan gum stock solution (A1) to Na-M / water solution, and stirring speed is increased to 300rpm-350rpm. Once xanthan gum is fully added and mixed, 1% konjac gum stock solution (A2) is added to Na-M / water / xanthan gum solution, and stirring speed is increased to 500rpm-550rpm. Then solid benefit agent is added to beaker under continuous stirring and is dispersed completely. Then composition is divided into three 60g plastic jars (Flak-Tech, Max 60 translucent cup, catalog number 501222t): one jar is filled to 50ml, and two jars are filled to 25ml. Sample is kept at 60 ℃ for one hour, and then cooled at room temperature (25 ± 3 ℃) until solid. 50ml sample is measured for firmness with firmness test method, and 50ml sample is measured for thermal stability by thermal stability test method. Water extrusion test method is carried out to two 25ml samples for water extrusion measurement. The representative data demonstrate that the prototypes exhibit desirable properties for these rheological solid compositions even in the presence of a suspending agent.
[0258] Table 1
[0259]
[0260]
[0261] Table 2
[0262]
[0263] Table 3
[0264]
[0265]
[0266] Table 4
[0267]
[0268] Table 5
[0269]
[0270]
[0271] Table 6
[0272]
[0273] Table 7
[0274]
[0275]
[0276] Table 8
[0277]
[0278] Example 2
[0279] Examples AF-BO used fixed gum suspension systems with different levels and compositions of crystallizing agents. The suspension was made of 65 wt% x-gum and 35 wt% k-gum, for a total of 0.05 wt%, which was the optimal blend described in Example 1. The composition of the crystallizing agents sodium myristate, sodium palmitate, and sodium stearate was plotted on the x-axis; the crystallizing agent content was plotted on the y-axis ( Figure 5). The "X" mark indicates a composition with a stability rating of "0" as determined by the Phase Stability Test Method, and is a comparative composition; the "" mark indicates a composition with a stability rating of "1" as determined by the Phase Stability Test Method, and is a preferred composition of the present invention; the "O" mark indicates a composition with a stability rating of "2" as determined by the Phase Stability Test Method, and is the most preferred composition. Surprisingly, these data show that suspending agents can significantly affect the stability of the composition, and in these examples even a moderate amount of suspending agent can cause the composition to liquefy, requiring an increase in the content of crystallizing agent to form a stable composition. It is also surprising that the suspending agent affects the shorter chain length crystallizing agent (i.e., sodium myristate) to a greater extent than the longer chain length crystallizing agent (i.e., sodium stearate), as evidenced by the former requiring more crystallizing agent. Tables 9-17 also contain firmness (firmness test method), temperature (thermal stability test method), and work (water extrusion test method) data for representative compositions of the present invention, indicating that even in the presence of a suspending agent, the prototypes exhibit the desired properties of these rheological solid compositions.
[0280] Preparation of composition
[0281] Samples were prepared using a heated mixing apparatus. An overhead mixer (IKA, Model RW20DMZ) and three-blade impeller design were assembled. All preparations were heated on a heating pad assembly (VWR, 7x7 CER Hotplate, Catalog No. NO97042-690) with heating controlled by an attached probe. All preparations were carried out in 250 ml stainless steel beakers (Fischer Scientific).
[0282] Prepare the NaM / water solution by first adding the preservatives (1, 2). Then add water (3) and sodium myristate (4) to the beaker. Place the beaker on a heating pad assembly. Place an overhead stirrer in the beaker and set to rotate at 100 rpm. Set the heater to 80°C. Heat the preparation to 80°C. Turn off the heat and allow the preparation to cool to 60°C.
[0283] Final preparation is prepared by adding 1% xanthan gum stock solution (A1) to Na-M / water solution, and stirring speed is increased to 300rpm-350rpm. Once xanthan gum is fully added and mixed, 1% konjac gum stock solution (A2) is added to Na-M / water / xanthan gum solution, and stirring speed is increased to 500rpm-550rpm. Then solid benefit agent is added to beaker under continuous stirring and is dispersed completely. Then composition is divided into three 60g plastic jars (Flak-Tech, Max 60 translucent cup, catalog number 501222t): one jar is filled to 50ml, and two jars are filled to 25ml. Sample is kept at 60 ℃ for one hour, and then cooled at room temperature (25 ± 3 ℃), until solid. Firmness measurement is carried out to 50ml sample with firmness test method, and thermal stability measurement is carried out to 50ml sample by thermal stability test method. Water extrusion measurement is carried out to two 25ml samples by water extrusion test method. The representative data demonstrate that the prototypes exhibit desirable properties for these rheological solid compositions even in the presence of a suspending agent.
[0284] Table 9
[0285]
[0286]
[0287] Table 10
[0288]
[0289] Table 11
[0290]
[0291] Table 12
[0292]
[0293] Table 13
[0294]
[0295] Table 14
[0296]
[0297]
[0298] Table 15
[0299]
[0300] Table 16
[0301]
[0302]
[0303] Table 17
[0304]
[0305] Example 3
[0306] This example demonstrates the use of Figure 4 and Figure 5 The suspending agent described in the present invention effectively suspends the composition of the perfume capsules (PC) (which are considered to be representative of the insoluble encapsulated active agent). The perfume capsules have an oil core surrounded by a thin solid shell. Without being bound by theory, since the density of the perfume is less than that of the aqueous phase, the capsules will float to the top of the composition in the absence of a suspending agent. The sample of the present invention with the suspending agent (Sample BP) was demonstrated to have a stability rating of "2" as determined by the Phase Stability Test Method, while the comparative sample without the suspending agent (Sample BQ) was demonstrated to have a stability rating of "0" as determined by the Phase Stability Test Method.
[0307] Preparation of composition
[0308] The composition of the present invention is prepared by adding Euxyl PE 9010 (1), Symdiol 68 (2), water (3) and sodium myristate (4) to a stainless steel beaker (Beaker Griffin 250 mL stainless steel beaker, VWR catalog number: 74360-008, or equivalent). The beaker is placed on a heating pad assembly (VWR hot plate with thermocouple, SN: 160809002) and an overhead stirrer (IKA RW20DZM.n overhead mixer, SN: 03.153609) is placed in the beaker and set to rotate at 100 rpm. The heater is set to 80°C. The preparation is heated to 80°C. Once the solution reaches 80°C, the solution is cooled to 60°C, at which time the x-gum (A1) and k-gum (A2) solutions are added along with the PC (13). The mixer is increased by 100 rpm for each addition of an ingredient. The solution was then divided into three 60 g plastic jars (Flak-Tech, Max 60 translucent cup, catalog number 501222t): one jar was filled to 50 ml and two jars were filled to 25 ml. The samples were kept at 60°C for one hour and then cooled at room temperature (25±3°C) until solid. The 50 ml sample was measured for firmness using the firmness test method, and the 50 ml sample was measured for thermal stability by the thermal stability test method. Two 25 ml samples were measured for water extrusion by the water extrusion test method. The representative data show that the prototypes exhibit the desired properties of these rheological solid compositions even in the presence of a suspending agent.
[0309] A comparative composition was prepared by adding Euxyl PE 9010 (1), Symdiol 68 (2), water (3) and sodium myristate (4) to a stainless steel beaker (Beaker Griffin 250 mL stainless steel beaker, VWR catalog number: 74360-008, or equivalent). The beaker was placed on a heating pad assembly (VWR hot plate with thermocouple, SN: 160809002) and an overhead stirrer (IKA RW20DZM.n overhead mixer, SN: 03.153609) was placed in the beaker and set to rotate at 100 rpm. The heater was set to 80°C. The preparation was heated to 80°C. Once the solution reached 80°C, the solution was cooled to 60°C and PC (13) was added. The mixer was increased by 100 rpm for each addition of an ingredient. The solution was then divided into three 60 g plastic jars (Flak-Tech, Max 60 translucent cup, catalog number 501222t): one jar was filled to 50 ml and two jars were filled to 25 ml. The samples were kept at 60° C. for one hour and then cooled at room temperature (25±3° C.) until solid. The 50 ml sample was subjected to firmness measurement using the Firmness Test Method, and the 50 ml sample was subjected to thermal stability measurement by the Thermal Stability Test Method. The two 25 ml samples were subjected to water extrusion measurement by the Water Extrusion Test Method.
[0310] Table 18
[0311]
[0312] Example 4
[0313] This example demonstrates the use of Figure 4 and Figure 5 The suspending agent described in the present invention is effective to suspend the starch composition, which is considered to be representative of the insoluble active particles that settle. The starch is added to provide a silky feel to the skin and surfaces. Without being bound by theory, since the starch is denser than the water phase and is insoluble, it will settle in the water phase. The sample of the present invention with the suspending agent (Sample BR) was demonstrated to have a stability rating of "2" as determined by the Phase Stability Test Method, while the comparative sample without the suspending agent (Sample BS) was demonstrated to have a stability rating of "0" as determined by the Phase Stability Test Method.
[0314] Preparation of composition
[0315] The inventive sample was prepared by adding Euxyl PE 9010 (1), Symdiol 68 (2), water (3) and sodium myristate (4) to a stainless steel beaker (Beaker Griffin 250 mL stainless steel beaker, VWR catalog number: 74360-008, or equivalent). The beaker was placed on a heating pad assembly (VWR hot plate with thermocouple, SN: 160809002) and an overhead stirrer (IKA RW20DZM.n overhead mixer, SN: 03.153609) was placed in the beaker and set to rotate at 100 rpm. The heater was set to 80°C. The preparation was heated to 80°C. Once the solution reached 80°C, the solution was cooled to 60°C, at which time the X-gum (A1) and K-gum (A2) solutions were added along with the starch (10). The mixer was increased by 100 rpm for each addition of an ingredient. The composition was then divided into three 60 g plastic jars (Flak-Tech, Max 60 translucent cup, catalog number 501222t): one jar was filled to 50 ml and two jars were filled to 25 ml. The samples were kept at 60°C for one hour and then cooled at room temperature (25±3°C) until solid. The 50 ml sample was measured for firmness using the Firmness Test Method, and the 50 ml sample was measured for thermal stability by the Thermal Stability Test Method. Two 25 ml samples were measured for water extrusion by the Water Extrusion Test Method. The representative data show that the prototypes exhibit the desired properties of these rheological solid compositions even in the presence of a suspending agent.
[0316] Comparative samples were prepared by adding Euxyl PE 9010 (1), Symdiol 68 (2), water (3) and sodium myristate (4) to a stainless steel beaker (Beaker Griffin 250 mL stainless steel beaker, VWR catalog number: 74360-008, or equivalent). The beaker was placed on a heating pad assembly (VWR hot plate with thermocouple, SN: 160809002) and an overhead stirrer (IKA RW20DZM.n overhead mixer, SN: 03.153609) was placed in the beaker and set to rotate at 100 rpm. The heater was set to 80°C. The preparation was heated to 80°C. Once the solution reached 80°C, the solution was cooled to 60°C and starch (10) was added. The mixer was increased by 100 rpm for each addition of an ingredient. The composition was then divided into three 60 g plastic jars (Flak-Tech, Max 60 translucent cup, catalog number 501222t): one jar was filled to 50 ml and two jars were filled to 25 ml. The samples were kept at 60° C. for one hour and then cooled at room temperature (25±3° C.) until solid. The 50 ml sample was subjected to firmness measurement using the Firmness Test Method and the 50 ml sample was subjected to thermal stability measurement by the Thermal Stability Test Method. The two 25 ml samples were subjected to water extrusion measurement by the Water Extrusion Test Method.
[0317] Table 19
[0318]
[0319]
[0320] Example 5
[0321] This example demonstrates the use of Figure 4 and Figure 5 The suspending agent described in the present invention effectively suspends the composition of coconut oil, which is considered to be a representative of liquid-solid insoluble active agents. Coconut oil is used as an emollient on skin and hair. In the process of preparing these compositions, coconut oil is melted into a liquid and then emulsified in the stirred composition. After cooling, the oil hardens into solid particles. Without being bound by theory, since the oil is less dense than the composition, the oil will float to the top of the mixture in the absence of a suspending agent. The sample of the present invention with a suspending agent (sample BT) was found to have a stability grade of "2" as measured by the phase stability test method, while the comparative sample without a suspending agent (sample BU) was found to have a stability grade of "0" as measured by the phase stability test method.
[0322] Preparation of composition
[0323] The inventive sample was prepared by adding Euxyl PE 9010 (1), Symdiol 68 (2), water (3) and sodium myristate (4) to a stainless steel beaker (Beaker Griffin 250 mL stainless steel beaker, VWR catalog number: 74360-008, or equivalent). The beaker was placed on a heating pad assembly (VWR hot plate with thermocouple, SN: 160809002) and an overhead stirrer (IKA RW20DZM.n overhead mixer, SN: 03.153609) was placed in the beaker and set to rotate at 100 rpm. The heater was set to 80°C. The preparation was heated to 80°C. Once the solution reached 80°C, the solution was cooled to 60°C, at which time the x-gum (A1) and k-gum (A2) solutions were added along with the coconut oil (12). The mixer was increased by 100 rpm for each addition of an ingredient. The composition was then divided into three 60 g plastic jars (Flak-Tech, Max 60 translucent cup, catalog number 501222t): one jar was filled to 50 ml and two jars were filled to 25 ml. The samples were kept at 60°C for one hour and then cooled at room temperature (25±3°C) until solid. The 50 ml sample was measured for firmness using the Firmness Test Method, and the 50 ml sample was measured for thermal stability by the Thermal Stability Test Method. Two 25 ml samples were measured for water extrusion by the Water Extrusion Test Method. The representative data show that the prototypes exhibit the desired properties of these rheological solid compositions even in the presence of a suspending agent.
[0324] A comparative sample was prepared by adding Euxyl PE 9010 (1), Symdiol 68 (2), water (3), and sodium myristate (4) to a stainless steel beaker (Beaker Griffin 250 mL stainless steel beaker, VWR catalog number: 74360-008, or equivalent). The beaker was placed on a heating pad assembly (VWR hot plate with thermocouple, SN: 160809002), and an overhead stirrer (IKA RW20DZM.n overhead mixer, SN: 03.153609) was placed in the beaker and set to rotate at 100 rpm. The heater was set to 80°C. The preparation was heated to 80°C. Once the solution reached 80°C, the composition was cooled to 60°C, at which time coconut oil (12) was added. The mixer was increased by 100 rpm for each addition of an ingredient. The composition was then divided into three 60 g plastic jars (Flak-Tech, Max 60 translucent cup, catalog number 501222t): one jar was filled to 50 ml and two jars were filled to 25 ml. The samples were kept at 60° C. for one hour and then cooled at room temperature (25±3° C.) until solid. The 50 ml sample was subjected to firmness measurement using the Firmness Test Method and the 50 ml sample was subjected to thermal stability measurement by the Thermal Stability Test Method. The two 25 ml samples were subjected to water extrusion measurement by the Water Extrusion Test Method.
[0325] Table 20
[0326]
[0327] Example 6
[0328] This example demonstrates the use of Figure 4 and Figure 5 The suspending agent described in the present invention effectively suspends the composition of peppermint oil, which is considered to be a representative of liquid insoluble active agents. Peppermint oil is a natural essential oil used for natural treatment of skin and hair. The oil remains liquid throughout the preparation process. Without being bound by theory, it will float to the top of the composition in the absence of a suspending agent because it is less dense than the water phase. Surprisingly, these oils also "interfere" with the crystallization process of the crystallizing agent, so the content of the crystallizing agent needs to be adjusted for the presence of oil. The examples of the present invention with suspending agents are proven to have a stability grade of "2" as determined by the phase stability test method (samples BV and BX), while the comparative examples without suspending agents (sample BZ) have a stability grade of "0" as determined by the phase stability test method. Sample BY containing a suspending agent shows a stability grade of "0" as determined by the phase stability test method, which is due to the high amount of peppermint oil, which causes the failure of stability and firmness.
[0329] Preparation of composition
[0330] The inventive sample was prepared by adding Euxyl PE 9010 (1), Symdiol 68 (2), water (3) and sodium myristate (4) to a stainless steel beaker (Beaker Griffin 250 mL stainless steel beaker, VWR catalog number: 74360-008, or equivalent). The beaker was placed on a heating pad assembly (VWR hot plate with thermocouple, SN: 160809002) and an overhead stirrer (IKA RW20DZM.n overhead mixer, SN: 03.153609) was placed in the beaker and set to rotate at 100 rpm. The heater was set to 80°C. The preparation was heated to 80°C. Once the solution reached 80°C, the solution was cooled to 60°C, at which time the x-gum (A1) and k-gum (A2) solutions were added along with the peppermint oil (11). The mixer was increased by 100 rpm for each addition of an ingredient. The composition was then divided into three 60 g plastic jars (Flak-Tech, Max 60 translucent cups, catalog number 501222t): one jar was filled to 50 ml and two jars were filled to 25 ml. The samples were kept at 60°C for one hour and then cooled at room temperature (25±3°C) until solid. The 50 ml sample was measured for firmness using the firmness test method, and the 50 ml sample was measured for thermal stability using the thermal stability test method. The two 25 ml samples were measured for water extrusion using the water extrusion test method. The representative data show that the prototype exhibits the desired properties of these rheological solid compositions even in the presence of a suspending agent. The representative data show that the prototype exhibits the desired properties of these rheological solid compositions even in the presence of a suspending agent.
[0331] Comparative samples were prepared by adding Euxyl PE 9010 (1), Symdiol 68 (2), water (3) and sodium myristate (4) to a stainless steel beaker (VWR hot plate with thermocouple, SN: 160809002). The beaker was placed on a heating pad assembly (details) and an overhead stirrer (IKA RW20DZM.n overhead mixer, SN: 03.153609) was placed in the beaker and set to rotate at 100 rpm. The heater was set to 80°C. The preparation was heated to 80°C. Once the solution reached 80°C, the solution was cooled to 60°C and peppermint oil (11) was added. The mixer was increased by 100 rpm for each addition of an ingredient. The composition was then divided into three 60 g plastic jars (Flak-Tech, Max 60 translucent cups, catalog number 501222t): one jar was filled to 50 ml and two jars were filled to 25 ml. The sample was kept at 60°C for one hour and then cooled at room temperature (25±3°C) until solid. The firmness was measured on a 50 ml sample using the firmness test method, and the thermal stability was measured on a 50 ml sample using the thermal stability test method. Water extrusion was measured on two 25 ml samples using the water extrusion test method.
[0332] Table 21
[0333]
[0334] Example 7
[0335] This example shows that a stable composition with a very complex mixture of a large amount of insoluble active agents can be formed, and the composition can sometimes be modified. All compositions contain about 10% by weight of insoluble active agents, and all compositions contain a blend of seven different oils (see oil blends). Those skilled in the art consider this to be a very large amount of dispersed insoluble active agents. Samples CA, CB and CC utilize a 0.09% by weight x-gum and k-gum blend suspending agent system (see Example 1). As previously described, some oils require the amount of crystallizing agent to be adjusted. In this example, it is increased to about 5% by weight to compensate for the weakening effect associated with the presence of oil. Relative to the previous examples with 0.3% by weight-2.0% by weight insoluble active agent particles, the amount of suspension in sample CA is still too small to stabilize the composition. In samples CB and CC, NaCl is added to improve the thermal stability of the composition, so that the crystallizing agent crystallizes faster than originally. Comparative sample CD omits the suspending agent, which causes the oil to be almost completely separated at the top of the composition in the form of a thick layer, making it unsuitable for consumer use.
[0336] (A3) Preparation of oil blend
[0337] The following ingredients were weighed and added to a 1-liter beaker: L-menthol (14), nutmeg oil (15), camphor (16), eucalyptus oil (17), cedar leaf oil (18), rosin with antioxidant (19), thymol NF (20). They were mixed using an overhead mixer set rotating at 100 rpm until the solution was completely clear, and then mixed for an additional 10 minutes.
[0338] Preparation of composition
[0339] Deionized water (3) is added to a 16oz wide-mouth glass bottle (VWR, catalog number: glc-01700). Sodium chloride (21) is added to the wide-mouth bottle. The wide-mouth bottle is vortexed until the sodium chloride is completely dissolved. It is then placed in a 90°C controlled water bath (Insta-therm 2600mL, controlled by Staco INC Variable autotransformer) and the mixture is allowed to reach bath temperature. A large magnetic stirring bar is placed in the wide-mouth bottle and rotated at 200rpm. Sodium palmitate (8) is added to the wide-mouth bottle. It is loosely capped to prevent water loss and to prevent pressurization. The mixture is stirred until the sodium palmitate is completely dissolved. The wide-mouth bottle is removed from the water bath and placed in a second 80°C controlled water bath (VWR 7x7 Stir PRO, with temperature probe). The first cap is replaced with a second cap containing two 8mm holes: one hole is located in the center to accommodate the impeller shaft, and one hole is offset halfway between the edge and the center of the jar to allow the addition of the remaining ingredients. The 4-blade impeller is installed by passing the shaft through the center hole in the cover and placing the blades in the mixture when the cover is tightened. The impeller is set to rotate at 450rpm (Caframo BDC 3030). Euxyl PE (1) and Symdiol 68 (2) are added through the second hole in the cover, and x-gum (A1) and k-gum (A2) stock solutions are also added through the second hole using a 1ml positive displacement syringe. After mixing for one minute, the oil blend (A3) is added through the same hole. The impeller speed is increased to 750rpm and maintained for another two minutes. The final mixture is poured into a 60ml cup (Flak-Tech, Max 60 translucent cup, catalog number 501222t) to cool and crystallize. The firmness test method is used to measure the firmness, and the 50ml sample is subjected to the thermal stability test method. The water extrusion test method is used to measure the water extrusion of two 25ml samples.
[0340] Table 22
[0341]
[0342] Example 8
[0343] The present embodiment shows that by increasing the amount of suspending agent, a stable composition with a very complex mixture of a large amount of insoluble active agents can be formed. All compositions contain an insoluble active agent of about 10% by weight-12% by weight, and all compositions contain a blend (see vaseline / oil blend) of six different oils (sample CF) and vaseline (sample CE), wherein x-gum is used as a suspending agent with an elevated concentration. It is particularly important to have a higher concentration of x-gum, because vaseline is a liquid at process temperature and is converted into a solid at room temperature. Each composition uses about 0.30% by weight of x-gum as a suspending agent. This is a significantly higher concentration than when x-gum and k-gum are combined as a mixture in Example 1 and emphasized in Example 7. Without being bound by theory, compared with the gum blend, a single x-gum increases the viscosity of the composition before forming a mesh. In addition, the amount of the crystallizing agent is increased to about 5% by weight to compensate for the weakening effect associated with the presence of oil in the composition. The larger the content of the suspending agent, the higher the stability.
[0344] (A4) Preparation of X-gum stock solution in glycerol
[0345] The x-gum stock solution was prepared by adding 9.001 grams of glycerol (9) to a 60 ml Speed Mixer cup (Flak-Tech, Max 60 translucent cup, order number: 501222t). 1.007 grams of x-gum (5) was added to the cup. It was placed in a Speed Mixer (Flacktek, Inc.) and run at 3500 rpm for one minute. The mixture was allowed to stand for one hour, at which time it was mixed for another 10 seconds at 3500 rpm.
[0346] (A5) Preparation of oil blend
[0347] The following materials were weighed and added to a 1-liter beaker: L-menthol (14), nutmeg oil (15), camphor (16), eucalyptus oil (17), cedar leaf oil (18), thymol NF (20). They were mixed using an overhead impeller mixer at 100 rpm until the solution was completely clear, then mixed for an additional 10 minutes.
[0348] (A6) Vaseline / Oil Blend
[0349] 10.227 g of the oil mixture (A5) was preheated to 40° C. in a glass vial on a hot plate (VWR Digital Heat Block, Cat. No. 12621-088) along with 14.02 g of petrolatum (22). It was then vortexed at maximum speed for 10 seconds and returned to the 40° C. hot plate for no longer than 60 minutes before being used to prepare the example compositions.
[0350] Preparation of composition
[0351] Deionized water (3) was added to a 16oz wide-mouth glass bottle (VWR). Sodium chloride (21) was added to the wide-mouth bottle. The wide-mouth bottle was vortexed until the salt was completely dissolved. It was then placed in a 90°C controlled water bath (Insta-therm 2600mL, controlled by a StacoINC Variable autotransformer) and the mixture was allowed to reach bath temperature. A large magnetic stir bar was placed in the wide-mouth bottle and rotated at 200rpm. Sodium palmitate (8) was added to the wide-mouth bottle. It was loosely capped to prevent water loss while preventing pressurization. The mixture was stirred until the sodium palmitate was completely dissolved. The wide-mouth bottle was removed from the water bath and placed in a second 80°C controlled water bath (VWR 7x7 Stir PRO, with temperature probe). The first cap was replaced with a second cap containing two 8mm holes: one hole was located in the center to accommodate the impeller shaft, and one hole was offset halfway between the edge and the center of the jar to allow the addition of the remaining ingredients. A 4-blade impeller was installed by passing the shaft through the center hole in the cap and placing the blades into the mixture when the cap was tightened. The impeller is set to rotate at 450rpm (Caframo BDC 3030). Then, Euxyl PE (1) and Symdiol 68 (2) are added through the second hole in the lid. A 1ml positive displacement syringe is used to drop the glycerol stock solution of x-gum (A4) through the second hole. After mixing for one minute, the oil / petroleum jelly blend (A6) is added through the same hole. The impeller speed is increased to 750rpm and maintained for another two minutes. The final mixture is poured into a 60ml cup (Flak-Tech, Max 60 translucent cup, order number: 501222t) to cool and crystallize. The firmness is measured using the firmness test method, and the 50ml sample is subjected to thermal stability measurement by the thermal stability test method; the water extrusion measurement is performed on two 25ml samples by the water extrusion test method. The representative data show that the prototype exhibits the desired properties of these rheological solid compositions even in the presence of a suspending agent.
[0352] Table 23
[0353]
[0354] Example 9
[0355] These samples show that using microfibers as a suspending agent, a composition of the present invention can be formed having a very complex mixture of a large weight percentage of an insoluble active agent with about 10 weight percent of a blend of seven different oils and petrolatum (Samples CG and CH). Without being bound by theory, it is believed that the microfibers increase the viscosity of the composition prior to forming a network. Both compositions are stable without sodium chloride (Sample CG) or with sodium chloride (CH) to increase the thermal stability of the composition, causing the crystallizing agent to crystallize faster than it would otherwise. Microfibers greater than 0.2 weight percent to 0.27 weight percent are able to effectively suspend the insoluble active agent, similar to Example 7.
[0356] (A7) Vaseline / Oil Blend
[0357] 10.227 g of the oil mixture (A5) was preheated to 40° C. in a glass vial on a hot plate (VWR Digital Heat Block, Cat. No. 12621-088) along with 14.02 g of petrolatum (22). The vial was then vortexed at maximum speed for 10 seconds and returned to the 40° C. hot plate for no longer than 60 minutes before being used to prepare the example compositions.
[0358] Preparation of composition
[0359] Deionized water (3) was added to a 16oz wide-mouth glass bottle (VWR). Rheocrysta c-2sp solution (24) was added dropwise using a 1ml positive displacement syringe. Sodium chloride (21) was added to the wide-mouth bottle. The wide-mouth bottle was vortexed until the salt was completely dissolved. It was then placed in a 90°C controlled water bath (Insta-therm 2600mL, controlled by Staco INC Variable autotransformer) and the mixture was allowed to reach bath temperature. A large magnetic stirring bar was placed in the wide-mouth bottle and rotated at 200rpm. Sodium palmitate (8) was added to the wide-mouth bottle. It was loosely capped to prevent water loss while preventing pressurization. The mixture was stirred until the sodium palmitate was completely dissolved. The wide-mouth bottle was removed from the water bath and placed in a second 80°C controlled water bath (VWR 7x7 Stir PRO, with temperature probe). The first cap was replaced with a second cap containing two 8mm holes: one hole was located in the center device for the impeller shaft, and one hole was offset in the middle of the edge and the center of the tank device to add the remaining ingredients. The 4-blade impeller is installed by passing the shaft through the center hole in the cover and placing the blades into the mixture when the cover is tightened. The impeller is set to rotate at 450rpm (Caframo BDC 3030). Then, Euxyl PE (1) and Symdiol 68 (2) are added through the second hole in the cover. After mixing for one minute, the oil / petroleum jelly blend (A7) or oil mixture (A3) is added through the same hole. The impeller speed is increased to 750rpm and maintained for another two minutes. The final mixture is poured into a 60ml cup (Flak-Tech, Max 60 translucent cup, order number: 501222t) to cool and crystallize.
[0360] Table 24
[0361]
[0362]
[0363] Example 10
[0364] These samples show that using the laponite clay as a suspending agent, it is possible to form compositions of the invention containing a very complex mixture of insoluble active agents in large weight percentages, with the mixture having a blend of seven different oils and petrolatum at about 10 weight percent (Samples CI and CJ). Without being bound by theory, it is believed that the electrostatic attraction between the laponite clay particles creates a card box structure that creates a yield stress in the composition prior to network formation. As with Examples 8 and 9, higher levels of suspending agent can form a stable composition (Sample CI). Surprisingly, the addition of sodium chloride (Sample CJ) results in an unstable product compared to the previous Examples 7-9. In this case, one skilled in the art recognizes that the addition of sodium chloride eliminates the electrostatic attraction between the laponite clay particles and does not form a card box structure.
[0365] (A8) Preparation of synthetic hectorite solution
[0366] A 5% Laponite XLG stock was prepared using 2.500 g Laponite XLG (c4039229) and 47.512 g Di water, high speed mixed at 3500 rpm for 1 minute, and left to stand overnight. Water was then added to the jar. The synthetic hectorite stock solution was then added and stirred into solution using a 134:1 Q-line stirrer set to 25 on the dial with a 4-blade impeller. The salt was then added. The jar was then capped. It was then placed in a 90°C water bath, sodium palmitate was added, and stirred using a stir bar in the water bath until a turbid, uniform solution was formed. It was then placed in a second container at 80°C.
[0367] (A9) Vaseline / Oil Blend
[0368] The following were weighed and added to a 1 liter beaker: L-menthol (14); nutmeg oil (15); camphor (16); eucalyptus oil (17); cedar leaf oil (18); thymol (20). 10.227 g of this oil mixture and 14.02 g of petrolatum (22) were heated to 40° C. in a glass vial on a hot plate (VWR Digital Heating Block, catalog number 12621-088). The vial was then vortexed at maximum speed for 10 seconds and returned to the 40° C. hot plate for no longer than 60 minutes before use in preparing the example compositions.
[0369] (A10) Vaseline / oil blend
[0370] 5.040 g of the oil mixture (A5) and 5.046 g of petrolatum (22) were heated to 40° C. in a glass vial on a hot plate (VWR Digital Heat Block, Cat. No. 12621-088). The vial was then vortexed at maximum speed for 10 seconds and returned to the 40° C. hot plate for no longer than 60 minutes before being used to prepare the example compositions.
[0371] Preparation of composition
[0372] Deionized water (3) is added to a 16oz wide-mouth glass bottle (VWR). The synthetic hectorite solution (25) is also added dropwise through the second hole using a 1ml positive displacement syringe and mixed for another minute. Sodium chloride (21) is added to the wide-mouth bottle. The wide-mouth bottle is vortexed until the salt is completely dissolved. It is then placed in a 90°C controlled water bath (Insta-therm 2600mL, controlled by a Staco INCVariable autotransformer) and the mixture is brought to bath temperature. A large magnetic stirring bar is placed in the wide-mouth bottle and rotated at 200rpm. Sodium palmitate (8) is added to the wide-mouth bottle. It is loosely capped to prevent water loss and to prevent pressurization. The mixture is stirred until the sodium palmitate is completely dissolved. The wide-mouth bottle is removed from the water bath and placed in a second 80°C controlled water bath (VWR 7x7 Stir PRO, with temperature probe). The first cover was replaced with a second cover containing two 8 mm holes: one hole in the center device for the impeller shaft, and one hole offset between the edge and the center of the can device to add the remaining ingredients. The 4-blade impeller was installed by passing the shaft through the center hole in the cover and placing the blades into the mixture while tightening the cover. The impeller was set to rotate at 450 rpm (Caframo BDC 3030). Finally, the oil / petroleum jelly blend (A9) or (A10) was added through the same hole. The impeller speed was increased to 750 rpm and maintained for another two minutes. The final mixture was poured into a 60 ml cup (Flak-Tech, Max 60 translucent cup, order number: 501222t) to cool and crystallize.
[0373] Table 25
[0374]
[0375]
[0376] Embodiment 11
[0377] This example shows that even at slightly higher levels of suspending agent, a stable, commercially viable composition can be produced, which has a large and extremely complex mixture of about 25% by weight of insoluble active agents. It is believed that higher levels of insoluble active materials (IA%) such as petrolatum and insoluble oils allow for better sensory experiences such as the "feel" and "smell" of the composition to be recognized by the consumer when applied to the skin. In the absence of a suspending agent, both the petrolatum and the insoluble oil will separate from the water during the formation process. Without being bound by theory, it is believed that the suspending agent increases the viscosity of the composition during preparation (e.g., Example 1), preventing the separation of the insoluble active material and requiring even higher levels of suspending agent. Example 1 shows that the suspension of the insoluble active material requires a very small level of suspending agent, including only x-gum, provided that its level is high enough. Example 2 shows that increasing the level of suspending agent can significantly soften the composition (some do not crystallize at all), and requires additional crystallizing agents and salts. This example shows that up to 0.30 wt % x-gum can be utilized to produce a composition with 25 wt % insoluble active that meets the desired criteria for stability, thermal stability, firmness and water extrusion.
[0378] (A11) Preparation of X-Gum in Glycerol Stock Solution
[0379] The x-gum stock solution was prepared by adding 36.024 grams of glycerol (9) to a 60 ml Speed Mixer cup (Flak-Tech, Max 60 translucent cup, order number: 501222t). 4.015 grams of x-gum (5) was added to the cup. It was placed in a Speed Mixer (Flacktek, Inc.) and run at 3500 rpm for one minute. The mixture was allowed to stand for one hour, at which time it was mixed for another 10 seconds at 3500 rpm.
[0380] Preparation of composition
[0381] Part 1: Oil / Vaseline Mixture: Add the oil mixture (A3) to a glass vial and place in a heat block set at 60°C. Heat the petroleum jelly (22) until liquid and then add to the vial. Stir the vial and keep it in a heat block at 55°C until use.
[0382] Part 2: Sample Preparation: Deionized water (3) was added to a 16oz wide-mouth glass bottle (VWR). For samples CK-CR, all of the sodium chloride (21) was added to the wide-mouth bottle; in Example CS (first), part of the sodium chloride (21) was added. The wide-mouth bottle was vortexed until the salt was completely dissolved. It was then placed in a water bath (VWR 7x7 Stir PRO with temperature probe) and the temperature was controlled at 90°C. A magnetic stir bar was added to the mixture and set to rotate at 200 rpm, creating a vortex in the mixture. Sodium palmitate (8) was added to the mixture. The wide-mouth bottle was loosely capped to prevent water loss and to prevent pressurization. The mixture was stirred until the sodium palmitate was completely dissolved. The wide-mouth bottle was then removed from the first bath and placed in a second controlled water bath (VWR 7x7 Stir PRO with temperature probe) controlled at 80°C. The first cover is replaced with a second cover comprising two 8mm holes: one hole is centered for the impeller shaft, and one hole is offset in the middle of the edge and the center of the tank device to add the remaining ingredients. The 4-blade impeller is installed by passing the shaft through the center hole in the cover and placing the blades in the mixture when the cover is tightened. The impeller is rotated at 500rpm (Caframo BDC 3030). A syringe is used to slowly add xanthan collagen stock solution (A11) through the second hole. Finally, for sample CK-CR, oil / vaseline mixture (Part 1) and preservative (1) are added through the same hole; for sample CS, oil / vaseline mixture (Part 1), preservative (1) and surplus sodium chloride (21) (second) are added through the same hole. The impeller speed is increased to 1,000rpm and maintained for another two minutes. The final mixture is poured into a 60ml cup (Flak-Tech, Max 60 translucent cup, order number: 501222t) to cool and crystallize. The solution was then divided into three 60 g plastic jars (Flak-Tech, Max 60 translucent cup, catalog number 501222t): one jar was filled to 50 ml and two jars were filled to 25 ml. The samples were kept at 60° C. for one hour and then cooled at room temperature (25±3° C.) until solid. The 50 ml sample was subjected to firmness measurement using the Firmness Test Method, and the 50 ml sample was subjected to thermal stability measurement by the Thermal Stability Test Method. The two 25 ml samples were subjected to water extrusion measurement by the Water Extrusion Test Method.
[0383] Table 26
[0384]
[0385]
[0386] Table 27
[0387]
[0388] Table 28
[0389]
[0390]
[0391] Example 12
[0392] This example demonstrates a method for preparing a rheological solid personal care composition. A 5 kg batch of the rheological solid personal care composition was prepared according to the following procedure:
[0393] First, water, NaCl, and NaOH were added to the main mixing vessel (a 2-gallon Ross mixer with planetary and high shear mixing elements). The heating and mixing of the main mixing vessel were turned on to provide the water phase. Once the main mixing vessel reached 70±5°C, palmitic acid as an emulsifier was added to the main mixing vessel and mixed for about 10 minutes to ensure neutralization to sodium palmitate. The main mixing vessel continued to heat to 80±5°C. Then, phenoxyethanol as a preservative and NaCl to improve the thermal stability of the final rheological solid personal care composition were added to the main mixing vessel.
[0394] Xanthan gum and glycerin were added to the first premix vessel (a stainless steel vessel with an overhead mixer equipped with a pitch blade mixing element) and mixed to ensure that the xanthan gum was dispersed within the glycerin. This suspension premix was then added to the main mixing vessel to increase the dispersed structure of the hydrophobic ingredients.
[0395] The petrolatum and fragrance are added to a second premix container (a stainless steel container with an overhead mixer equipped with a pitch blade mixing element) and heated to 40±5° C. while mixing to form a petrolatum-fragrance premix. The petrolatum-fragrance premix may contain an insoluble active, preferably a topical active selected from the group consisting of menthol, nutmeg, camphor, eucalyptus, cedar leaf, thymol, and any combination thereof.
[0396] The main mixing vessel is cooled to 65 ± 5 ° C, and the petrolatum-fragrance premix is added to the main mixing vessel. Sodium lactate as a hygroscopic component is further added to the main mixing vessel to stabilize the final crystalline structure of the rheological solid personal care composition. The main mixing vessel is then mixed for about 10 minutes. Cooling allows the sodium palmitate to crystallize, thereby encapsulating the hydrophilic and hydrophobic components.
[0397] The rheological solid personal care composition produced by the process may comprise the following components:
[0398] Table 29
[0399] Ingredient name Function of ingredients %w / w water Solvents 61.52 Sodium Lactate Hygroscopic stabilizer 3.33 Sodium chloride Temperature Stabilizer 3.00 Sodium hydroxide Base material 1.44 Palmitic acid Palmitate Precursor / Emulsifier 4.61 glycerin X-gum dispersant 2.70 Xanthan gum Structuring agent 0.30 Vaseline Stabilizer 8.00 Fragrance Fragrance 15.00 Phenoxyethanol preservative 0.10
[0400] Without being bound by theory, it is believed that the basic unit operations described in the 5 kg process can be scaled with the size of the batch. Therefore, it is expected that the same preparation method described in the 5 kg process is applicable to commercial scale batches such as 1,000 kg using a specific mixing tank. In addition, although described as a batch process, it is expected that such compositions can also be prepared in a continuous process.
[0401] Therefore, further, the order in which the components are added to the 5 kg batch process is non-limiting. The laboratory scale batches show that the order of addition can be adjusted (e.g., salt addition in Examples CR and CS). It is believed that the order of addition can also be adjusted in the commercial scale manufacturing process.
[0402] The release of fragrance compounds from the rheological solid personal care compositions of the present invention was evaluated using a selected ion flow tube mass spectrometer (SIFT-MS). The concentration profile describes the consumer experience, which includes a "burst" or intense release of fragrance upon application, followed by fragrance release for at least 15 minutes at concentrations above the odor detection threshold for a given fragrance. These data are shown in Figure 6 In the graph provided in FIG. 1 , the concentration (ppm) of the fragrance compounds is plotted against time (hours).
[0403] combination
[0404] A. A rheological solid personal care composition comprising: (a) a crystallizing agent; (b) a suspending agent; (c) an insoluble active material; and (d) an aqueous phase.
[0405] B. The rheological solid personal care composition according to paragraph A, wherein the crystallization agent is present in an amount of 0.01 wt % to 10 wt %, preferably 0.1 wt % to about 7 wt %, more preferably 1 wt % to about 7 wt % based on the weight of the rheological solid personal care composition.
[0406] C. The rheological solid personal care composition according to paragraph A or B, comprising 0.01 wt% to 2 wt%, preferably 0.05 wt% to 1 wt%, more preferably 0.1 wt% to 0.5 wt% of a suspending agent based on the weight of the rheological solid personal care composition.
[0407] D. The rheological solid personal care composition of any of the preceding paragraphs, comprising from 0.1 wt% to 30 wt%, preferably from 0.1 wt% to 25 wt%, more preferably from 0.5 wt% to 15 wt% of an insoluble active material, based on the weight of the rheological solid personal care composition.
[0408] E. The rheological solid personal care composition of any of the preceding paragraphs, wherein the crystallizing agent comprises a salt of a fatty acid containing from about 12 to about 20 carbon atoms.
[0409] F. The rheological solid personal care composition of any of the preceding paragraphs, wherein the crystallizing agent is a metal salt.
[0410] G. The rheological solid personal care composition according to paragraph F, wherein the metal salt is at least one of sodium stearate, sodium palmitate, and sodium myristate.
[0411] H. The rheological solid personal care composition of any of the preceding paragraphs, wherein the insoluble active material is an insoluble active particle comprising an insoluble oil.
[0412] I. The rheological solid personal care composition according to paragraph H, wherein the insoluble active particles further comprise a hydrophobic non-aqueous vehicle.
[0413] J. The rheological solid personal care composition according to paragraph I, wherein the rheological solid personal care composition comprises from about 1% to about 15%, preferably 3% to 12%, more preferably 5% to 10% by weight of the hydrophobic non-aqueous vehicle, based on the weight of the rheological solid personal care composition.
[0414] K. The rheological solid personal care composition of paragraph H, wherein the rheological solid personal care composition comprises from about 4 wt.% to about 10 wt.% of the insoluble oil.
[0415] L. The rheological solid personal care composition of any of the preceding paragraphs, wherein the suspending agent comprises a polysaccharide.
[0416] M. The rheological solid personal care composition of any of the preceding paragraphs, wherein the suspending agent comprises a first polysaccharide and a second polysaccharide, wherein the first polysaccharide is xanthan gum and the second polysaccharide is selected from the group consisting of konjac gum, locust bean gum, and combinations thereof.
[0417] N. The rheological solid personal care composition of any of the preceding paragraphs, having a stability rating of 1 or greater as determined by the Phase Stability Test Method.
[0418] O. The rheological solid personal care composition of any of the preceding paragraphs, having a thermal stability greater than about 30°C as determined by the Thermal Stability Test Method.
[0419] The dimensions and values disclosed herein are not to be understood as being strictly limited to the exact numerical values cited. Instead, unless otherwise indicated, each such dimension is intended to represent the stated value and a functionally equivalent range around that value. For example, a dimension disclosed as "40 mm" is intended to mean "about 40 mm".
[0420] The values disclosed herein as range ends should not be understood as being strictly limited to the exact numerical values cited. Instead, unless otherwise indicated, each numerical range is intended to represent the quoted value and any real number within the range, including integers. For example, a range disclosed as "1 to 10" is intended to represent "1, 2, 3, 4, 5, 6, 7, 8, 9, and 10", and a range disclosed as "1 to 2" is intended to represent "1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, and 2".
[0421] Unless expressly excluded or otherwise limited, each document cited herein, including any cross-referenced or related patent or patent application and any patent application or patent to which this application claims priority or the benefit of, is hereby incorporated by reference in its entirety. The citation of any document is not an admission that it is prior art to any of the present invention disclosed or claimed herein, or an admission that it, by itself or in combination with any one or more of the references, proposes, suggests, or discloses any such invention. In addition, to the extent that any meaning or definition of a term in this invention conflicts with any meaning or definition of the same term in a document incorporated by reference, the meaning or definition assigned to that term in this invention shall govern.
[0422] Although specific embodiments of the present invention have been illustrated and described, it will be apparent to those skilled in the art that various other changes and modifications may be made without departing from the spirit and scope of the present invention. Therefore, it is intended that all such changes and modifications within the scope of the present invention be covered in the appended claims.
Claims
1. A rheological solid personal care composition, comprising: a. Crystallization agent, wherein the crystallizing agent comprises a metal salt selected from sodium stearate, sodium palmitate, sodium myristate and mixtures thereof, and wherein the crystallization agent is present in an amount of 0.01% to 10% by weight of the rheologically solid personal care composition; b. Suspension concentrate; c. insoluble active substances; and d. water phase; wherein the rheological solid personal care composition comprises a crystalline network, The crystalline network comprises fibrous crystalline particles formed by the crystallization agent.
2. A rheological solid personal care composition, comprising: a. a crystallizing agent, wherein the crystallizing agent is sodium palmitate and is present in an amount of 1 wt % to 7 wt % based on the weight of the rheological solid personal care composition; b. a suspending agent, wherein the suspending agent is xanthan gum and is present at a level of 0.03 wt % to 0.3 wt % based on the weight of the rheologically solid personal care composition; c. an insoluble active, wherein the insoluble active is present in an amount of 0.3 wt % to 30 wt % based on the weight of the rheological solid personal care composition; and d. an aqueous phase; and e. wherein the rheological solid personal care composition has a stability temperature greater than 35°C as determined by the Thermal Stability Test Method.
3. The rheological solid personal care composition of claim 1 or 2, wherein the rheological solid personal care composition is characterized by at least one of the following characteristics: a. Firmness between 0.1N and 50.0N; b. Having thermal stability above 30°C; c. having a liquid extrusion between 100 J m-3 and 6000 J m-3; d. Having a stability rating of 1 or greater; e. Have a stability rating of 2 or greater.
4. The rheological solid personal care composition of claim 1, wherein the crystallizing agent is present in an amount of 1% to 7% by weight of the rheological solid personal care composition.
5. The rheological solid personal care composition of claim 1, wherein the suspending agent comprises a polysaccharide.
6. The rheological solid personal care composition of claim 5, wherein the polysaccharide comprises xanthan gum.
7. The rheological solid personal care composition of claim 5, wherein the total concentration of polysaccharides present in the rheological solid personal care composition is from 0.01 wt. % to 1.0 wt. % by weight of the rheological solid personal care composition.
8. The rheological solid personal care composition of claim 1 or 2, wherein the insoluble active comprises a topical active selected from the group consisting of menthol, nutmeg, camphor, eucalyptus, cedar leaf, thymol, and mixtures thereof.
9. The rheological solid personal care composition of claim 1 or 2, wherein the insoluble active comprises insoluble active particles comprising an insoluble oil.
10. The rheological solid personal care composition of claim 9, wherein said rheological solid personal care composition comprises from 4% to 15%, by weight of said composition, of said insoluble oil.
11. The rheological solid personal care composition of claim 1 or 2, wherein the rheological solid personal care composition further comprises a hydrophobic non-aqueous vehicle.
12. The rheological solid personal care composition of claim 11, wherein the hydrophobic non-aqueous vehicle comprises a material selected from the group consisting of liquid petrolatum, petrolatum, mineral oil, glycerin, synthetic oils, fats, silicones, silicone derivatives, polyvinyl acetate, natural waxes, synthetic waxes, hydrocarbons, hydrocarbon derivatives, vegetable waxes, vegetable oils, pentaerythritol tetraisostearate, and combinations thereof.
13. The rheological solid personal care composition of claim 11, wherein the hydrophobic non-aqueous vehicle comprises a material selected from the group consisting of liquid petrolatum, petrolatum, mineral oil, almond oil, canola oil, squalane, squalene, coconut oil, corn oil, jojoba oil, jojoba wax, lecithin, olive oil, safflower oil, sesame oil, shea butter, soybean oil, sweet almond oil, sunflower oil, tea tree oil, palm oil, fish oil, oleic acid, and mixtures thereof.
14. The rheological solid personal care composition of claim 11, wherein the hydrophobic non-aqueous vehicle comprises liquid petrolatum, petrolatum, or mixtures thereof.
15. The rheological solid personal care composition of claim 11, wherein said rheological solid personal care composition comprises from 1% to 15%, by weight of said rheological solid personal care composition, of said hydrophobic non-aqueous vehicle.
16. The rheological solid personal care composition of claim 1 wherein said fibrous crystalline particles are characterized by a length in the direction of their longest axis that is 10 times the length of the particles in any orthogonal direction.
17. The rheological solid personal care composition of claim 1 or 2, wherein the rheological solid personal care composition is in the form of a stick intended for topical application to the skin.
18. Use of the rheological solid personal care composition according to any one of claims 1 to 17 in the preparation of a medicament for treating nasal congestion, cold, flu, cough, dry cough, chest tightness or muscle aches and pains.
Citation Information
Patent Citations
Propylene glycol / glycerin-based deodorant
EP2170257A2
Propylene glycol / glycerin-based deodorant
EP2465487A2
Perfume delivery systems for consumer goods
US20070275866A1
Heavy-metal derivatives of 1-hydroxy-2-pyridinethiones and method of preparing same
US2809971A
Method of combatting dandruff with pyridinethiones metal salts detergent compositions
US3236733A